Water-soluble unit dose article

By using a second water-soluble film with high content of polyviriamid isozyme in the water-soluble single agent article, the problem that the water-soluble single agent article in the prior art cannot be completely dissolved under short-term and low-temperature washing conditions is achieved, and better solubility and packaging quality are achieved.

JP7648759B2Active Publication Date: 2025-03-18PROCTER & GAMBLE CO
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023530261
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-15
Filing Date
2021-12-15
Publication Date
2025-03-18
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

Existing water-soluble single agent articles may not be completely dissolved under short and low temperature washing conditions, resulting in undissolved film material remaining on the washed items.

Method used

A second water-soluble film containing high content of polyvirimidine (PVOH) isase is used, which maintains good solubility performance under short and low temperature washing conditions while reducing packaging defects.

Benefits of technology

Complete dissolution of water-soluble single agent articles under short and low temperature washing conditions was achieved, reducing the residue of undissolved film materials and improving the overall quality of the packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648759000006
    Figure 0007648759000006
  • Figure 0007648759000007
    Figure 0007648759000007
  • Figure 0007648759000001
    Figure 0007648759000001
Patent Text Reader

Abstract

Water-soluble unit dose articles and methods of manufacture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Water-soluble unit dose articles and methods of manufacture. [Background technology]

[0002] Water-soluble unit dose articles are popular with consumers because they are convenient and efficient to use. Such water-soluble unit dose articles often contain detergent compositions. Without being bound by theory, when the water-soluble unit dose article is added to water, the film dissolves / disintegrates, releasing its internal contents into the surrounding water and generating a cleaning solution. The film used must meet the dual criteria of providing sufficient strength so that it does not tear or break during storage and transportation, resulting in premature rupture of the water-soluble unit dose article, but dissolves sufficiently during the wash cycle to minimize undesirable film residue at the end of the wash operation. To meet these requirements, films composed of polyvinyl alcohol have been used. The preferred method of producing such unit dose articles is to deform a first water-soluble film in a mold to create an open cavity, fill the open cavity with a detergent composition, then close the open cavity with a second water-soluble film, and seal the first and second water-soluble films together to create the water-soluble unit dose article.

[0003] There is an increasing desire to wash fabrics under more environmentally friendly conditions, such as shorter wash cycles and cooler wash temperatures, under such conditions unit dose articles manufactured using conventional water-soluble films (including primarily polyvinyl alcohol homopolymers) can undergo incomplete dissolution during the wash cycle, resulting in residual undissolved film material that can deposit on the articles being washed.

[0004] Efforts have been made previously to overcome this problem. US Patent No. 10,619,042 teaches a water-soluble unit dose article comprising a water-soluble film containing a polyvinyl alcohol (PVOH) resin blend, the blend comprising a first PVOH polymer comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units, the carboxylated anionic monomer units being present in the first PVOH polymer in an amount of about 3 mol % to about 6 mol %, and a second PVOH polymer consisting essentially of vinyl alcohol monomer units and optionally vinyl acetate monomer units, the first PVOH polymer being present in an amount ranging from about 10% to about 70% by weight of the total PVOH polymer in the film. Such a water-soluble unit dose article provides both excellent dissolution and acceptable structural integrity as well.

[0005] However, the problem faced by such unit dose articles is not a lack of structural integrity of the film itself, but rather the possible failure of the seal between the first water-soluble film and the second water-soluble film, which can result in premature rupture of the water-soluble unit dose article. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] U.S. Patent No. 10619042 Summary of the Invention [Problem to be solved by the invention]

[0007] Thus, there is a need in the art for a water soluble unit dose article that provides reduced seal failure compared to U.S. Pat. No. 1,0619,042, while also maintaining the structural integrity and dissolution profile of the film itself equivalent to that of U.S. Pat. No. 1,0619,042.

[0008] Surprisingly, it has been found that the use of a water-soluble unit dose article according to the present invention accomplished this, which is even more surprising considering that the second water-soluble film contains a higher degree of polyvinyl alcohol homopolymer, which one skilled in the art would expect to result in reduced dissolution under short and cold wash cycles. [Means for solving the problem]

[0009] A first aspect of the present invention is a water-soluble unit dose article comprising at least a first compartment and a household care composition, the household care composition being contained within the at least first compartment, the unit dose article comprising: a. a first water-soluble film, the first water-soluble film having a first surface and a second surface, the first water-soluble film comprising a first polyvinyl alcohol (PVOH) resin, the first polyvinyl alcohol resin comprising: i. 1% to 65%, preferably 10% to 65%, preferably 20% to 60%, more preferably 30% to 50% by weight of a first polyvinyl alcohol resin comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units, wherein the carboxylated anionic monomer units are derived from a member selected from the group consisting of maleic acid, monoalkyl maleates, dialkyl maleates, maleic anhydride, and combinations thereof; ii. a first water-soluble film comprising a second PVOH polymer, the second PVOH polymer being 35% to 99% by weight, preferably 35% to 90% by weight, preferably 40% to 80% by weight, more preferably 50% to 70% by weight of a first polyvinyl alcohol resin, the second PVOH polymer being a homopolymer, the homopolymer being composed of vinyl alcohol monomer units and optionally vinyl acetate monomer units; b. a second water-soluble film, the second water-soluble film having a first surface and a second surface, the second water-soluble film comprising a second polyvinyl alcohol resin, the second polyvinyl alcohol resin comprising: i. less than 15% by weight of a second polyvinyl alcohol resin comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units, wherein the carboxylated anionic monomer units are derived from a member selected from the group consisting of maleic acid, monoalkyl maleates, dialkyl maleates, maleic anhydride, and combinations thereof; ii. a second water-soluble film comprising 85% to 100% by weight of a second polyvinyl alcohol resin, the polyvinyl alcohol homopolymer or homopolymer blend being composed of vinyl alcohol monomer units and, optionally, vinyl acetate monomer units; the second polyvinyl alcohol resin has an average 4% solution viscosity in deionized water at 20° C. in the range of 8 mPa.s to less than 12 mPa.s; A first side of the first water-soluble film is sealed to a second side of the second water-soluble film to create at least a first compartment between the first water-soluble film and the second water-soluble film.

[0010] A second aspect of the present invention is a process for producing a water soluble unit dose article according to any preceding claim, the process comprising: a. deforming a first water-soluble film in a mold via thermoforming, vacuum forming, or a combination thereof to create an open cavity; b. filling at least one open cavity with a household care composition; c. closing the filled open cavity with a second water-soluble film; and d. sealing the first water-soluble film and the second water-soluble film to create a water-soluble unit dose article, preferably the first water-soluble film and the second water-soluble film are sealed via a solvent seal, more preferably a solvent sealing solution is applied to the second side of the second water-soluble film prior to sealing the films together, and the second side of the second water-soluble film faces the first water-soluble film. [Brief description of the drawings]

[0011] [Figure 1] A water-soluble unit dose article according to the present invention. [Diagram 2] A schematic diagram of the basic setup for pouch strength pass rate % and seal failure % tests is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Water-soluble unit dose article A first aspect of the present invention is a water-soluble unit dose article. The water-soluble unit dose article comprises at least a first compartment and a household care composition. The household care composition is contained in at least one compartment. The household care composition is described in more detail below. The water-soluble unit dose article comprises a first water-soluble film and a second water-soluble film, and optionally a third water-soluble film. The first water-soluble film, the second water-soluble film, and the optional third water-soluble film are described in more detail below.

[0013] The water-soluble unit dose article comprises a water-soluble film that is molded such that the unit dose article comprises at least one internal compartment surrounded by the water-soluble film.The water-soluble unit dose article is configured such that the household care composition does not leak out of the compartment during storage.However, when the water-soluble unit dose article is added to water, the water-soluble film dissolves and the contents of the internal compartment are released into the cleaning solution.

[0014] Compartment should be understood to mean the closed internal space within the unit dose article that holds the household care composition.

[0015] The first water-soluble film has a first side and a second side. The second water-soluble film has a first side and a second side. The optional third water-soluble film has a first side and a second side.

[0016] A first side of the first water-soluble film is sealed to a second side of the second water-soluble film to create a first compartment between the first and second water-soluble films. Optionally, a first side of the second water-soluble film is sealed to a second side of a third water-soluble film to create at least a second compartment between the second and third water-soluble films, the second compartment being positioned above the first compartment.

[0017] Preferably, the first water-soluble film and the second water-soluble film are sealed via solvent sealing, heat sealing, or a combination thereof, preferably via solvent sealing. More preferably, the solvent sealing solution comprises an aqueous solvent, a non-aqueous solvent, or a mixture thereof. Even more preferably, the solvent sealing solution comprises water. Preferably, the solvent sealing solution comprises at least 95% by weight, or even at least 98% by weight, or even at least 99% by weight, or even 100% by weight of the solvent sealing solution. The solvent sealing solution can be applied to the film by any suitable method, including contact and / or non-contact methods. For example, the solvent solution can be applied in a contact transfer process, for example, using a contact member comprising a non-absorbent or substantially impermeable material, for example, using an anilox roller, a rubber (e.g., EPDM) roller, or any combination thereof, optionally in combination with a doctor blade. The sealing solution can be applied using a drawdown bar, a Mayer bar, or a similar device. The sealing solution may be applied using a contact member comprising an absorbent material, such as natural felt, synthetic felt, porous plastic, foam, sponge, microfiber, cotton, polyester, extruded polyester fiber, nonwoven webs, etc., for example in the form of a pad or roller. The sealing solution may be applied via an injection nozzle or a spray nozzle. Any combination of the aforementioned methods and devices is contemplated. Preferably, the solvent sealing solution is applied via a felt roll, via an injection nozzle, a spray nozzle, or a combination thereof, more preferably via a felt roll. Preferably, the solvent sealing solution is applied to the second side of the second water-soluble film, and the second side of the second water-soluble film faces the first side of the first water-soluble film.

[0018] Preferably, the second water-soluble film and the optional third water-soluble film are sealed via solvent sealing, heat sealing, or a combination thereof, preferably via solvent sealing. More preferably, the solvent sealing solution comprises an aqueous solvent, a non-aqueous solvent, or a mixture thereof. Even more preferably, the solvent sealing solution comprises water. Preferably, the solvent sealing solution comprises at least 95% by weight, or even at least 98% by weight, or even at least 99% by weight, or even 100% by weight of the solvent sealing solution. The solvent sealing solution can be applied to the film by any suitable method, including contact and / or non-contact methods. For example, the solvent solution can be applied in a contact transfer process, for example, using a contact member comprising a non-absorbent or substantially impermeable material, for example, using an anilox roller, a rubber (e.g., EPDM) roller, or any combination thereof, optionally in combination with a doctor blade. The sealing solution can be applied using a drawdown bar, a Mayer bar, or a similar device. The sealing solution may be applied using a contact member comprising an absorbent material, such as natural felt, synthetic felt, porous plastic, foam, sponge, microfiber, cotton, polyester, extruded polyester fiber, nonwoven webs, etc., for example in the form of a pad or roller. The sealing solution may be applied via an injection nozzle or a spray nozzle. Any combination of the above methods and devices is contemplated. Preferably, the solvent sealing solution is applied via a felt roll, via a spray nozzle or an injection nozzle, or a combination thereof, more preferably via a felt roll. Preferably, the solvent sealing solution is applied to a first side of the second water-soluble film, and the first side of the second water-soluble film faces the second side of the third water-soluble film.

[0019] Surprisingly, it has been found that when prior art films are sealed via solvent sealing, the solvent sealing solution tends not to be deposited homogeneously on the water-soluble film before sealing. Without wishing to be bound by theory, if two films are intended to be sealed together, the solvent sealing solution needs to be applied to at least one of the films. If the solvent sealing solution does not provide a homogeneous layer on the film to which it is applied, this may result in a weaker seal between the two films, leading to sealing failure and premature breakage of the water-soluble unit dose article. Surprisingly, it has been found that in the unit dose article according to the present invention, a more uniform / homogenous layer of the solvent sealing solution is obtained between the water-soluble films to be sealed, resulting in reduced sealing failure. Without wishing to be bound by theory, it is believed that the addition of the solvent sealing solution on the water-soluble film may create a thin foam layer. This thin foam layer results in a non-homogeneous layer of sealing solution present on the water-soluble film, leading to premature sealing failure. Surprisingly, it has been found that the addition of a solvent sealing solution to the second water-soluble film according to the present invention results in a reduction or even absence of a foam layer and therefore reduced instances of sealing failure.

[0020] Optionally, the unit dose article comprises at least a third compartment, preferably at least a third and a fourth compartment, between the second water-soluble film and the third water-soluble film. Preferably, the second and third compartments, preferably the second, third and fourth compartments, are positioned next to each other, and the second and third compartments, preferably the second, third and fourth compartments, are positioned above the first compartment. Preferably, the second and third compartments, or the second, third and fourth compartments, are smaller than the first compartment. The second and third compartments, or the second, third and fourth compartments, may be the same size as each other or may be different sizes. Some of the compartments may be the same size and some may be different sizes.

[0021] The household care composition according to the present invention may be contained in at least one of the compartments. For example, the detergent composition may be contained in only one compartment, or in two compartments, or even in three compartments, or even in four compartments.

[0022] Each compartment may contain the same composition or different compositions. The different compositions may all be in the same form or they may be in different forms.

[0023] Figure 1 discloses a water soluble unit dose article (1) according to the present invention. Shown is a first water soluble film (2) and a second water soluble film (3) sealed together at a sealing area (4). A liquid laundry detergent composition (5) is contained within the water soluble unit dose article (1).

[0024] Preferably, the water soluble unit dose article is coated with a lubricant, preferably the lubricant is selected from talc, zinc oxide, silica, siloxane, zeolite, silicic acid, alumina, sodium sulfate, potassium sulfate, calcium carbonate, magnesium carbonate, sodium citrate, sodium tripolyphosphate, potassium citrate, potassium tripolyphosphate, calcium stearate, zinc stearate, magnesium stearate, starch, modified starch, clay, kaolin, gypsum, cyclodextrin, or mixtures thereof.

[0025] First water-soluble film The water-soluble unit dose article comprises a first water-soluble film. The first water-soluble film of the present invention is water-soluble or water-dispersible. The first water-soluble film preferably has a thickness before deformation of 20 to 150 microns, preferably 35 to 125 microns, even more preferably 50 to 110 microns, and most preferably about 76 microns. The first water-soluble film has a first surface and a second surface.

[0026] Preferably, the first water-soluble film has a water solubility of at least 50%, preferably at least 75%, or even at least 95%, as measured by the following method presented herein after using a glass filter with a maximum pore size of 20 microns. 5 grams ± 0.1 grams of film material is added to a pre-weighed 3L beaker, and 2L ± 5ml of distilled water is added. This is vigorously stirred for 30 minutes at 30°C with a magnetic stirrer (Labline model number 1250 or equivalent and a 5cm magnetic stirrer) set at 600 rpm. The mixture is then filtered through a pleated qualitative sintered glass filter with a pore size defined above (maximum 20 micrometers). The water is dried from the collected filtrate by any conventional method, and the weight of the remaining material is determined (this is the dissolved or dispersed fraction). The percentage of solubility or dispersion can then be calculated.

[0027] The first water-soluble film material can be obtained by casting, blowing, extruding, or blown extrusion of polymeric materials as known in the art, preferably the first water-soluble film is a solvent cast water-soluble film.

[0028] The first water-soluble film comprises a first polyvinyl alcohol (PVOH) resin, the first polyvinyl alcohol resin comprising: i. 1% to 65%, preferably 10% to 65%, preferably 20% to 60%, more preferably 30% to 50% by weight of a first polyvinyl alcohol resin comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units, wherein the carboxylated anionic monomer units are derived from a member selected from the group consisting of maleic acid, monoalkyl maleates, dialkyl maleates, maleic anhydride, and combinations thereof; ii. A second PVOH polymer which is 35% to 99% by weight, preferably 35% to 90% by weight, preferably 40% to 80% by weight, more preferably 50% to 70% by weight of the first polyvinyl alcohol resin, wherein the second PVOH polymer is a homopolymer, the homopolymer comprising vinyl alcohol monomer units and optionally vinyl acetate monomer units.

[0029] Preferably, the first polyvinyl alcohol resin is present in the range of 50% to 95% by weight, or 50% to 80% by weight, more preferably 60% to 75% by weight of the first water-soluble film.

[0030] Preferably, the carboxylated anionic monomer units in the first water-soluble film are derived from monoalkyl maleate units, preferably monomethyl maleate, its salts, preferably alkali metal salts, and combinations thereof. Without wishing to be bound by theory, the polyvinyl alcohol polymer comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units is an anionic polyvinyl alcohol copolymer. Preferably, each carboxylated anionic monomer unit is present in the first polyvinyl alcohol polymer in an average amount of 3 mol% to 6 mol%, or 3 mol% to 5 mol%, or 3.5 mol% to 4.5 mol%, or 4 mol% to 4.5 mol%.

[0031] Without wishing to be bound by theory, the term "homopolymer" generally includes polymers having one type of monomer repeat unit (e.g., a polymer chain that includes or consists of a single monomer repeat unit). In particular, in the case of polyvinyl alcohol polymers, the term "homopolymer" further includes copolymers having a distribution of vinyl alcohol monomer units and optionally vinyl acetate monomer units (e.g., a polymer chain that includes or consists of vinyl alcohol monomer units and vinyl acetate monomer units) depending on the degree of hydrolysis. When the hydrolysis is 100%, the polyvinyl alcohol homopolymer can only include vinyl alcohol units. Without wishing to be bound by theory, the term "copolymer" generally includes polymers having two or more types of monomer repeat units (e.g., a polymer chain that includes or consists of two or more different monomer repeat units, whether it is a random copolymer, a block copolymer, etc.). In particular, for polyvinyl alcohol polymers, the term "copolymer" (or "polyvinyl alcohol copolymer") can include copolymers having a distribution of vinyl alcohol and vinyl acetate monomer units, as well as at least one other type of monomer repeat unit, depending on the degree of hydrolysis (e.g., ter (or higher) polymer chains containing or consisting of vinyl alcohol, vinyl acetate, and one or more other monomer units, such as anionic monomer units). When hydrolysis is 100%, the polyvinyl alcohol copolymer may include copolymers having vinyl alcohol units and one or more other monomer units, but no vinyl acetate units. Without wishing to be bound by theory, the term "anionic copolymer" includes copolymers having anionic monomer units that contain anionic moieties. Common types of anionic monomer units include vinyl monocarboxylic acid monomers, their esters and anhydrides, dicarboxylic acid monomers with polymerizable double bonds, their esters and anhydrides, vinyl sulfonic acid monomers, and vinyl polymerized units corresponding to the alkali metal salts of any of the foregoing.Examples of the anionic monomer unit include vinyl polymerization units corresponding to vinyl anionic monomers, and examples of the vinyl anionic monomers include vinyl acetate, maleic acid, monoalkyl maleates, dialkyl maleates, monomethyl maleates, dimethyl maleates, maleic anhydride, fumaric acid, monoalkyl fumarate, dialkyl fumarate, monomethyl fumarate, dimethyl fumarate, fumaric anhydride, itaconic acid, monomethyl itaconate, dimethyl itaconate, itaconic anhydride, vinyl sulfonic acid, allyl sulfonic acid, ethylene sulfonic acid, 2-acrylamido-1-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-methylacrylamido-2-methylpropanesulfonic acid, 2-sulfoethyl acrylate (2-sufoethyl Examples of anionic monomers include acrylamidomethylpropanesulfonic acid (e.g., 2-acrylamido-1-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-methylacrylamido-2-methylpropanesulfonic acid), alkali metal salts thereof (e.g., sodium salts, potassium salts, or other alkali metal salts), esters of the foregoing (e.g., methyl, ethyl, or other C1-C4 or C6 alkyl esters), and combinations thereof (e.g., multiple types of anionic monomers, or equivalent forms of the same anionic monomer). The anionic monomer may include one or more acrylamidomethylpropanesulfonic acids (e.g., 2-acrylamido-1-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid), alkali metal salts thereof (e.g., sodium salts), and combinations thereof.

[0032] Preferably, the first polyvinyl alcohol polymer in the first water-soluble film is a. an average 4% aqueous solution viscosity (in deionized water) at 20°C of 10 mPa.s to 40 mPa.s, or 10 mPa.s to 30 mPa.s, or 12 mPa.s to 25 mPa.s, or 14 mPa.s to 20 mPa.s; or b. an average degree of hydrolysis of 60% to 99%, preferably 80% to 98%, preferably 83% to 95%, preferably 85% to 92%, or c. Characterized by a combination of these.

[0033] Preferably, the second polyvinyl alcohol polymer in the first aqueous solution is a. an average 4% aqueous solution viscosity (in deionized water) at 20°C of 3 mPa.s to 30 mPa.s, or 7 mPa.s to 30 mPa.s, or 10 mPa.s to 30 mPa.s, or 12 mPa.s to 25 mPa.s; or b. an average degree of hydrolysis of 60% to 99%, preferably 80% to 98%, preferably 85% to 95%, preferably 87% to 92%, or c. Characterized by a combination of these.

[0034] The viscosity of polyvinyl alcohol is determined by measuring freshly prepared solutions using a Brookfield LV type viscometer equipped with a UL adapter as described in the British Standard EN ISO15023-2:2006 Annex E Brookfield Test method. It is international practice to specify the viscosity of a 4% aqueous solution of polyvinyl alcohol at 20°C.

[0035] Preferably, the relative weight ratio of the first PVOH polymer and the second PVOH polymer in the first water-soluble film is from 90 / 10 to 10 / 90, preferably from 80 / 20 to 20 / 80, more preferably from 70 / 30 to 50 / 50.

[0036] The water-soluble films, including the first, second, and optional third water-soluble films, may be characterized or tested for tensile stress according to the Modulus (MOD) test as follows. This procedure involves determining the modulus at 10% elongation according to ASTM D 882 ("Standard Test Method for Tensile Properties of Thin Plastic Sheeting") or equivalent. An INSTRON tensile testing machine (Model 5544 Tensile Tester or equivalent) is used to collect the film data. A minimum of three test specimens are cut from each with a reliable cutting tool to ensure dimensional stability and repeatability, and tested in the machine direction (MD) (if applicable) for each measurement. Testing is performed in a standard laboratory atmosphere of 23±2.0°C and 35±5% relative humidity. A 1-inch (2.54 cm) wide specimen of a single film sheet with a thickness of 75 μm is prepared. The specimen is then transferred to the INSTRON tensile testing machine for testing with minimal exposure to a 35% relative humidity environment. The tensile tester is equipped with a 500N load cell and is prepared and calibrated according to the manufacturer's instructions. The appropriate grips and faces are attached (INSTRON grips with rubber coated 25mm wide faces, model number 2702-032, or equivalent). Samples are mounted in the tensile tester and analyzed to determine the 100% modulus (i.e., the stress required to obtain 100% film elongation).

[0037] The first water-soluble film has a modulus of at least about 20 N / mm2 as measured by the MOD test at 35% RH. 2The MOD value may be characterized by a 100% modulus value of at least about 20, 21, 22, 23, 24, 25, or 27 N / mm. Generally, a higher MOD value is desirable because the pouches are stiffer and less likely to deform or stick to each other when stacked together during manufacturing or in the final consumer package. Furthermore, the MOD value at 10% elongation corresponds to the film's ability to remain stiff rather than loosen and sag when in contact with liquid pouch contents. In particular, a film having a higher MOD value corresponds to a pouch that is less likely to soften and take on a loose, sagging appearance when in contact with liquid pouch contents containing low molecular weight polyol. In various embodiments, the first water-soluble film has a modulus of at least about 20, 21, 22, 23, 24, 25, or 27 N / mm. 2 , and / or up to about 24, 25, 27, 28, 29, or 30 N / mm 2 (For example, about 20N / mm 2 ~Approx. 30N / mm 2 , or about 20N / mm 2 ~about 28N / mm 2 , or about 22N / mm 2 ~Approx. 25N / mm 2 ) MOD value.

[0038] Preferably, the first water-soluble film comprises 0.1% to 3.5% by weight of the water-soluble film, or 0.1% to 2.5% by weight, or 1% to 2% by weight, or 0.5% to 2% by weight. Suitable surfactants can include nonionic, cationic, anionic, and zwitterionic classes. Suitable surfactants include, but are not limited to, nonionic surfactants, including but not limited to polyoxyethylenated polyoxypropylene glycols, alcohol ethoxylates, alkylphenol ethoxylates, tertiary acetylenic glycols, and alkanolamides; cationic surfactants, including but not limited to polyoxyethylenated amines, quaternary ammonium salts, and quaternized polyoxyethylenated amines; and zwitterionic surfactants, including but not limited to amine oxides, N-alkyl betaines, and sulfobetaines. For example, nonionic surfactants can be selected from alcohol ethoxylates, cationic surfactants can be selected from quaternary ammonium salts, and zwitterionic surfactants can be selected from amine oxides. Other suitable surfactants include dioctyl sodium sulfosuccinate, lactylated fatty acid esters of glycerol and propylene glycol, lactylic esters of fatty acids, sodium alkyl sulfates, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, lecithin, acetylated fatty acid esters of glycerol and propylene glycol, and acetylated esters of fatty acids, and combinations thereof.

[0039] Preferably, the first water-soluble film has a residual moisture content, as measured by Karl Fischer titration, of at least 4%, more preferably in the range of 4% to 15%, and even more preferably 5% to 10% by weight of the first water-soluble film.

[0040] Preferably, the first water-soluble film comprises one or more ingredients selected from the group consisting of plasticizers, plasticizer compatibilizers, lubricants, release agents, fillers, extenders, crosslinkers, antiblocking agents, antioxidants, detackifying agents, antifoaming agents, nanoparticles, bleaching agents, surfactants, and combinations thereof.

[0041] Preferably, the first water-soluble film comprises one or more plasticizers in an amount ranging from 5% to 50% by weight of the first water-soluble film, preferably 10% to 40% by weight, most preferably 20% to 30% by weight. Preferably, the plasticizer in the first water-soluble film is selected from a polyol, a sugar alcohol, or a mixture thereof, preferably, the polyol comprises a polyol selected from the group consisting of glycerol, diglycerin, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycols of 400 MW or less, neopentyl glycol, 1,2-propylene glycol, 1,3-propanediol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, and polyether polyols, or a mixture thereof, and the sugar alcohol comprises a sugar alcohol selected from the group consisting of isomalt, maltitol, sorbitol, xylitol, erythritol, adonitol, dulcitol, pentaerythritol, and mannitol, or a mixture thereof. Most preferably, the plasticizer is selected from the group consisting of sorbitol, glycerol, dipropylene glycol, polyethylene glycol, trimethylolpropane, and mixtures thereof.

[0042] Preferably, the first water-soluble film includes a lubricant / release agent. Suitable lubricants / release agents include, but are not limited to, fatty acids and their salts, fatty alcohols, fatty acid esters, fatty amines, fatty amine acetates, and fatty acid amides. Preferred lubricants / release agents are fatty acids, fatty acid salts, and fatty amine acetates. The amount of lubricant / release agent in the first water-soluble film ranges from 0.02% to 1.5% by weight, preferably 0.1% to 1% by weight, of the first water-soluble film.

[0043] Preferably, the first water-soluble film comprises a filler, a spreading agent, an antiblocking agent, a tackiness release agent, or a mixture thereof. Suitable fillers, extenders, antiblocking agents, tackiness release agents, or mixtures thereof include, but are not limited to, starch, modified starch, crosslinked polyvinylpyrrolidone, crosslinked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, and mica. Preferred materials are starch, modified starch, and silica. Preferably, the amount of fillers, spreading agents, antiblocking agents, tackiness release agents, or mixtures thereof in the first water-soluble film ranges from 0.1% to 25% by weight of the first water-soluble film, preferably from 1% to 10% by weight, more preferably from 2% to 8% by weight, and most preferably from 3% to 5% by weight. In the absence of starch, one preferred range of suitable fillers, spreading agents, anti-tack agents, detackifying agents, or mixtures thereof is 0.1% to 1%, preferably 4%, more preferably 6%, even more preferably 1% to 4%, and most preferably 1% to 2.5% by weight of the first water-soluble film.

[0044] The first water-soluble film may comprise a printed area. The printed area may be obtained using standard techniques such as flexographic printing or inkjet printing.

[0045] The first water-soluble film may include an aversive agent, such as a bitter agent. Suitable bitter agents include, but are not limited to, naringin, sucrose octaacetate, quinine hydrochloride, denatonium benzoate, or mixtures thereof. Any suitable concentration of the aversive agent may be used in the film. Suitable concentrations include, but are not limited to, 1-5000 ppm, or even 100-2500 ppm, or even 250-2000 ppm.

[0046] Preferably, the first water-soluble film and each individual component thereof independently contain from 0 ppm to 20 ppm, preferably from 0 ppm to 15 ppm, more preferably from 0 ppm to 10 ppm, even more preferably from 0 ppm to 5 ppm, even more preferably from 0 ppm to 1 ppm, even more preferably from 0 ppb to 100 ppb, and most preferably 0 ppb dioxane. Those skilled in the art will recognize known methods and techniques for determining dioxane levels within water-soluble films and their components.

[0047] Second water-soluble film The water-soluble unit dose article includes a second water-soluble film. The second water-soluble film has a first side and a second side. The second water-soluble film includes a second polyvinyl alcohol resin.

[0048] The second water-soluble film of the present invention is water-soluble or water-dispersible. The second water-soluble film preferably has an average thickness before deformation of 20 to 150 microns, preferably 35 to 125 microns, even more preferably 50 to 110 microns, and most preferably about 76 microns.

[0049] Preferably, the second water-soluble film has a water solubility of at least 50%, preferably at least 75%, or even at least 95%, as measured by the following method presented herein after using a glass filter with a maximum pore size of 20 microns. 5 grams ± 0.1 grams of film material is added to a pre-weighed 3L beaker and 2L ± 5ml of distilled water is added. This is vigorously stirred for 30 minutes at 30°C with a magnetic stirrer (Labline model number 1250 or equivalent and a 5cm magnetic stirrer) set at 600 rpm. The mixture is then filtered through a pleated qualitative sintered glass filter with a pore size defined above (maximum 20 micrometers). The water is dried from the collected filtrate by any conventional method, and the weight of the remaining material is determined (this is the dissolved or dispersed fraction). The percentage of solubility or dispersion can then be calculated.

[0050] The second water-soluble film material may be obtained by casting, blowing, extruding, or blown extrusion of polymeric materials as known in the art, preferably the second water-soluble film is a solvent cast water-soluble film.

[0051] The second water-soluble film contains a polyvinyl alcohol resin. The polyvinyl alcohol resin may be present in an amount of 50% to 95% by weight, preferably 50% to 80% by weight, and more preferably 60% to 75% by weight of the second water-soluble film.

[0052] The second polyvinyl alcohol resin comprises less than 15% by weight of the second polyvinyl alcohol resin of a polyvinyl alcohol polymer comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units, the carboxylated anionic monomer units being derived from a member selected from the group consisting of maleic acid, monoalkyl maleates, dialkyl maleates, maleic anhydride, and combinations thereof. Without wishing to be bound by theory, the polyvinyl alcohol polymer comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units is an anionic polyvinyl alcohol copolymer. The second polyvinyl alcohol resin also comprises 85% to 100% by weight of the second polyvinyl alcohol resin of a polyvinyl alcohol homopolymer or polyvinyl alcohol homopolymer blend, the polyvinyl alcohol homopolymer consisting of vinyl alcohol monomer units and optionally vinyl acetate monomer units.

[0053] The invention includes a second water-soluble film, the second water-soluble film includes a second polyvinyl alcohol resin, the second polyvinyl alcohol resin includes less than 15% by weight of the second polyvinyl alcohol resin of a polyvinyl alcohol polymer including carboxylated anionic monomer units derived from monoalkyl maleate units, preferably monomethyl maleate, a salt thereof, preferably an alkali metal salt, and combinations thereof. When present, preferably the carboxylated anionic monomer units are present in an average amount of at least 3 mol%, or 3 mol% to 6 mol%, or 3 mol% to 5 mol%, or 3.5 mol% to 4.5 mol%, or 4 mol% to 4.5 mol% in the polyvinyl alcohol polymer including the carboxylated anionic monomer units. If present, the polyvinyl alcohol polymer comprising the carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units in the polyvinyl alcohol resin of the second water-soluble film is preferably characterized by an average 4% aqueous solution viscosity (in deionized water) at 20° C. of from 10 mPa.s to 40 mPa.s, or from 10 mPa.s to 30 mPa.s, or from 12 mPa.s to 25 mPa.s, or from 14 mPa.s to 20 mPa.s, or an average degree of hydrolysis of from 60% to 99%, preferably from 80% to 98%, preferably from 83% to 95%, preferably from 85% to 92%, or a combination thereof.

[0054] Preferably, the carboxylated anionic units are derived from maleic acid, monoalkyl maleates, dialkyl maleates, monomethyl maleate, dimethyl maleate, maleic anhydride, or mixtures thereof, and more preferably, the maleic acid units are derived from monoalkyl maleate units, preferably selected from the group consisting of monomethyl maleate, its salts, preferably alkali metal salts, and combinations thereof.

[0055] The second polyvinyl alcohol resin also comprises a polyvinyl alcohol homopolymer or a polyvinyl alcohol homopolymer blend, with the polyvinyl alcohol homopolymer consisting of vinyl alcohol monomer units and optionally vinyl acetate monomer units, more preferably the second water-soluble film comprises a polyvinyl alcohol resin comprising 90% to 100% by weight of the polyvinyl alcohol resin, more preferably 100% by weight of the polyvinyl alcohol resin, a polyvinyl alcohol homopolymer or a polyvinyl alcohol homopolymer blend.

[0056] Most preferably, the polyvinyl alcohol resin of the second water-soluble film comprises a blend of a first polyvinyl alcohol homopolymer and a second polyvinyl alcohol homopolymer, the blend of the first and second polyvinyl alcohol homopolymers having an average viscosity, measured as a 4% polyvinyl alcohol solution in deionized water at 20° C., of 8 mPa.s or more but less than 12 mPa.s, preferably 10 mPa.s or more and less than 12 mPa.s, and preferably the first polyvinyl alcohol homopolymer and the second polyvinyl alcohol homopolymer are present in a relative weight ratio of 90 / 10 to 10 / 90, preferably 80 / 20 to 20 / 80, more preferably 70 / 30 to 50 / 50. Herein, the first polyvinyl alcohol homopolymer preferably has an average viscosity in the range of 11 mPa.s to 20 mPa.s, preferably 11 mPa.s to 15 mPa.s, measured as a 4% polyvinyl alcohol polymer solution in deionized water at 20° C., and the second polyvinyl alcohol homopolymer has an average viscosity in the range of 1 mPa.s to 10 mPa.s, preferably 5 mPa.s to 10 mPa.s, measured as a 4% polyvinyl alcohol polymer solution in deionized water at 20° C. More preferably, the delta average viscosity of the first polyvinyl alcohol homopolymer and the second polyvinyl alcohol homopolymer is at least 1 mPa.s, preferably 2 to 10 mPa.s, more preferably 3 to 8 mPa.s, measured as a 4% polyvinyl alcohol polymer solution in deionized water at 20° C. More preferably, the first and second polyvinyl alcohol homopolymers have an average degree of hydrolysis in the range of 75% to 99%, preferably 80% to 95%, most preferably 85% to 95%. More preferably, the polyvinyl alcohol resin of the second water-soluble film has an average degree of hydrolysis in the range of 75% to 99%, preferably 80% to 95%, and most preferably 85% to 95%. A suitable test method for measuring the degree of hydrolysis is according to the standard method JIS K6726.

[0057] The second water-soluble film had a modulus of 20 N / mm2 as measured by the MOD test at 35% RH. 2Generally, higher MOD values ​​(e.g., 20 N / mm 2 A modulus of elasticity of about 100% (or more) is desirable because it makes the films stiffer and less likely to deform and stick to each other when stacked on top of each other during manufacturing or in the final consumer package. Furthermore, the MOD value at 100% elongation corresponds to the ability of the film to remain stiff rather than loosen and sag when in contact with liquid pouch contents. In particular, a film having a higher MOD value corresponds to a pouch that is less likely to soften and take on a loose, saggy appearance when in contact with liquid pouch contents containing low molecular weight polyols. However, it has been determined that the second polyvinyl alcohol film can advantageously have a lower 100% modulus as described herein. Furthermore, when used as an intermediate film in a stacked pouch configuration as described herein, the relatively low MOD value and the resulting tendency of the film to sag is countered by the configuration of the pouch in which the second film is essentially entirely within the pouch product. The second water-soluble film has a modulus of elasticity of about 20 N / mm 2 Less than or about 19N / mm 2 Less than or about 18N / mm 2 Less than or about 17N / mm 2 Less than or about 16N / mm 2 Less than or about 15N / mm 2 Less than or about 14N / mm 2 less than, and optionally at least about 9 N / mm 2 , or at least about 10 N / mm 2 , or at least about 11 N / mm 2 , at least about 12 N / mm 2 , or at least about 13 N / mm 2 , for example, about 10 N / mm 2 ~Approx. 16N / mm 2 , or about 11 N / mm 2 ~Approx. 15N / mm 2 , or about 12N / mm 2 ~Approx. 14N / mm 2In a related embodiment, the second water-soluble film can have a MOD value in the range of at least about 1 N / mm from the 100% modulus value of the first water-soluble film. 2 , or at least about 2 N / mm 2 , or at least about 3 N / mm 2 , or at least about 4 N / mm 2 , or at least about 5 N / mm 2 , or at least about 6 N / mm 2 , or at least about 7 N / mm 2 , or at least about 10 N / mm 2 , or at least about 20 N / mm 2 , or at least about 25 N / mm 2 and optionally, at least about 1 N / mm2 greater than the 100% modulus value of any third water-soluble film. 2 , or at least about 2 N / mm 2 , or at least about 3 N / mm 2 , or at least about 4 N / mm 2 , or at least about 5 N / mm 2 , or at least about 6 N / mm 2 , or at least about 7 N / mm 2 , or at least about 10 N / mm 2 , or at least about 20 N / mm 2 and, still further optionally, the 100% modulus value of both the first water-soluble film and the optional third water-soluble film are at least about 1 N / mm 2 , or at least about 2 N / mm 2 , or at least about 3 N / mm 2 , or at least about 4 N / mm 2 , or at least about 5 N / mm 2 , or at least about 6 N / mm 2 , or at least about 7 N / mm 2 , or at least about 10 N / mm 2 , or at least about 20 N / mm 2 They may be characterized as different.

[0058] The second polyvinyl alcohol resin has an average viscosity of 8 mPa.s or more but less than 12 mPa.s, preferably 10 mPa.s or more and less than 12 mPa.s, measured as a 4% polyvinyl alcohol solution in deionized water at 20°C. The viscosity of polyvinyl alcohol is determined by measuring a freshly prepared solution using a Brookfield LV type viscometer with a UL adapter, as described in the British Standard EN ISO15023-2:2006 Annex E Brookfield Test method. It is international practice to specify the viscosity of a 4% aqueous polyvinyl alcohol solution (in deionized water) at 20°C. It is well known in the art that the viscosity of aqueous solutions of water-soluble polymers (polyvinyl alcohol or other) correlates with the weight average molecular weight of the same polymer, and in many cases viscosity is used as a proxy for the weight average molecular weight.

[0059] Preferably, the second water-soluble film comprises 0.1% to 3.5% by weight of the water-soluble film, or 0.1% to 2.5% by weight, or 1% to 2% by weight, or 0.5% to 2% by weight. Suitable surfactants can include nonionic, cationic, anionic, and zwitterionic classes. Suitable surfactants include, but are not limited to, nonionic surfactants, including but not limited to polyoxyethylenated polyoxypropylene glycols, alcohol ethoxylates, alkylphenol ethoxylates, tertiary acetylenic glycols, and alkanolamides; cationic surfactants, including but not limited to polyoxyethylenated amines, quaternary ammonium salts, and quaternized polyoxyethylenated amines; and zwitterionic surfactants, including but not limited to amine oxides, N-alkyl betaines, and sulfobetaines. For example, nonionic surfactants can be selected from alcohol ethoxylates, cationic surfactants can be selected from quaternary ammonium salts, and zwitterionic surfactants can be selected from amine oxides. Other suitable surfactants include dioctyl sodium sulfosuccinate, lactylated fatty acid esters of glycerol and propylene glycol, lactylic esters of fatty acids, sodium alkyl sulfates, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, lecithin, acetylated fatty acid esters of glycerol and propylene glycol, and acetylated esters of fatty acids, and combinations thereof.

[0060] Preferably, the second water-soluble film has a residual moisture content, as measured by Karl Fischer titration, of at least 4%, more preferably in the range of 4% to 15%, and even more preferably 5% to 10% by weight of the second water-soluble film.

[0061] Preferably, the second water-soluble film comprises one or more ingredients selected from the group consisting of plasticizers, plasticizer compatibilizers, lubricants, release agents, fillers, extenders, crosslinkers, antiblocking agents, antioxidants, detackifying agents, antifoaming agents, nanoparticles, bleaching agents, surfactants, and combinations thereof.

[0062] Preferably, the second water-soluble film comprises one or more plasticizers in an amount ranging from 5% to 50% by weight of the second water-soluble film, preferably 10% to 40% by weight, most preferably 20% to 30% by weight. Preferably, the plasticizer in the second water-soluble film is selected from a polyol, a sugar alcohol, or a mixture thereof, preferably, the polyol comprises a polyol selected from the group consisting of glycerol, diglycerin, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycols of 400 MW or less, neopentyl glycol, 1,2-propylene glycol, 1,3-propanediol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, and polyether polyols, or a mixture thereof, and the sugar alcohol comprises a sugar alcohol selected from the group consisting of isomalt, maltitol, sorbitol, xylitol, erythritol, adonitol, dulcitol, pentaerythritol, and mannitol, or a mixture thereof. Most preferably, the plasticizer is selected from the group consisting of sorbitol, glycerol, dipropylene glycol, polyethylene glycol, trimethylolpropane, and mixtures thereof.

[0063] Preferably, the second water-soluble film includes a lubricant / release agent. Suitable lubricants / release agents include, but are not limited to, fatty acids and their salts, fatty alcohols, fatty acid esters, fatty amines, fatty amine acetates, and fatty acid amides. Preferred lubricants / release agents are fatty acids, fatty acid salts, and fatty amine acetates. The amount of lubricant / release agent in the second water-soluble film ranges from 0.02% to 1.5% by weight, preferably 0.1% to 1% by weight, of the second water-soluble film.

[0064] Preferably, the second water-soluble film comprises a filler, a spreading agent, an antiblocking agent, a detackifying agent, or a mixture thereof. Suitable fillers, extenders, antiblocking agents, detackifying agents, or mixtures thereof include, but are not limited to, starch, modified starch, crosslinked polyvinylpyrrolidone, crosslinked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, and mica. Preferred materials are starch, modified starch, and silica. Preferably, the amount of fillers, spreading agents, antiblocking agents, detackifying agents, or mixtures thereof in the second water-soluble film ranges from 0.1% to 25% by weight of the second water-soluble film, preferably from 1% to 10% by weight, more preferably from 2% to 8% by weight, and most preferably from 3% to 5% by weight. In the absence of starch, one preferred range of suitable fillers, spreading agents, anti-tack agents, detackifying agents, or mixtures thereof is 0.1% to 1%, preferably 4%, more preferably 6%, even more preferably 1% to 4%, and most preferably 1% to 2.5% by weight of the second water-soluble film.

[0065] The second water-soluble film may comprise printed areas, which may be obtained using standard techniques such as flexographic printing or inkjet printing.

[0066] The second water-soluble film may include an aversive agent, such as a bitter agent. Suitable bitter agents include, but are not limited to, naringin, sucrose octaacetate, quinine hydrochloride, denatonium benzoate, or mixtures thereof. Any suitable concentration of the aversive agent may be used in the film. Suitable concentrations include, but are not limited to, 1-5000 ppm, or even 100-2500 ppm, or even 250-2000 ppm.

[0067] Preferably, the second water-soluble film and each individual component thereof independently contains between 0 ppm and 20 ppm, preferably between 0 ppm and 15 ppm, more preferably between 0 ppm and 10 ppm, even more preferably between 0 ppm and 5 ppm, even more preferably between 0 ppm and 1 ppm, even more preferably between 0 ppb and 100 ppb, and most preferably 0 ppb dioxane. Those skilled in the art will recognize known methods and techniques for determining dioxane levels within water-soluble films and their components.

[0068] Optional third water-soluble film The water-soluble unit dose article optionally includes a third water-soluble film. The third water-soluble film of the present invention is water-soluble or water-dispersible. The third water-soluble film preferably has a thickness before deformation of 20 to 150 microns, preferably 35 to 125 microns, even more preferably 50 to 110 microns, and most preferably about 76 microns. The third water-soluble film has a first surface and a second surface.

[0069] Preferably, the third water-soluble film has a water solubility of at least 50%, preferably at least 75%, or even at least 95%, as measured by the following method presented herein after using a glass filter with a maximum pore size of 20 microns. 5 grams ± 0.1 grams of film material is added to a pre-weighed 3L beaker, and 2L ± 5ml of distilled water is added. This is vigorously stirred for 30 minutes at 30°C with a magnetic stirrer (Labline model number 1250 or equivalent and a 5cm magnetic stirrer) set at 600 rpm. The mixture is then filtered through a pleated qualitative sintered glass filter with a pore size defined above (maximum 20 micrometers). The water is dried from the collected filtrate by any conventional method, and the weight of the remaining material is determined (this is the dissolved or dispersed fraction). The percentage of solubility or dispersion can then be calculated.

[0070] The third water-soluble film material can be obtained by casting, blowing, extruding, or blown extrusion of polymeric materials as known in the art, preferably the third water-soluble film is a solvent cast water-soluble film.

[0071] The third water-soluble film comprises a third polyvinyl alcohol (PVOH) resin, the third polyvinyl alcohol resin comprising: i. a first polyvinyl alcohol polymer comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units, wherein the carboxylated anionic monomer units are derived from a member selected from the group consisting of maleic acid, monoalkyl maleates, dialkyl maleates, maleic anhydride, and combinations thereof; ii. A second PVOH polymer, wherein the second PVOH polymer is a PVOH homopolymer, wherein the PVOH homopolymer comprises vinyl alcohol monomer units and optionally vinyl acetate monomer units.

[0072] Preferably, the third polyvinyl alcohol resin is present in the range of 50% to 95% by weight, or 50% to 80% by weight, more preferably 60% to 75% by weight of the third water-soluble film.

[0073] Preferably, the carboxylated anionic monomer units in the third water-soluble film are derived from monoalkyl maleate units selected from the group consisting of monomethyl maleate, its salts, preferably alkali metal salts, and combinations thereof. Preferably, each carboxylated anionic monomer unit is present in the first polyvinyl alcohol polymer of the third polyvinyl alcohol resin in an average amount of 3 mol% to 6 mol%, or 3 mol% to 5 mol%, or 3.5 mol% to 4.5 mol%, or 4 mol% to 4.5 mol%.

[0074] Preferably, the first polyvinyl alcohol polymer in the third water-soluble film is a. an average 4% aqueous solution viscosity (in deionized water) at 20°C of 10 mPa.s to 40 mPa.s, or 10 mPa.s to 30 mPa.s, or 12 mPa.s to 25 mPa.s, or 14 mPa.s to 20 mPa.s; or b. an average degree of hydrolysis of 60% to 99%, preferably 80% to 98%, preferably 83% to 95%, preferably 85% to 92%, or c. Characterized by a combination of these.

[0075] Preferably, the second polyvinyl alcohol polymer in the third water-soluble film is a. an average 4% aqueous solution viscosity (in deionized water) at 20°C of 3 mPa.s to 30 mPa.s, or 7 mPa.s to 30 mPa.s, or 10 mPa.s to 30 mPa.s, or 12 mPa.s to 25 mPa.s; or b. an average degree of hydrolysis of 60% to 99%, preferably 80% to 98%, preferably 85% to 95%, preferably 87% to 92%, or c. Characterized by a combination of these.

[0076] Preferably, in the third water-soluble film, the relative weight ratio of the first PVOH polymer and the second PVOH polymer is from 90 / 10 to 10 / 90, preferably from 80 / 20 to 20 / 80, more preferably from 70 / 30 to 50 / 50.

[0077] The third water-soluble film has a modulus of at least about 20 N / mm2 as measured by the MOD test at 35% RH. 2 The MOD value may be characterized by a 100% modulus value of at least about 20, 21, 22, 23, 24, 25, or 27 N / mm. Generally, a higher MOD value is desirable because the pouches are stiffer and less likely to deform or stick to each other when stacked together during manufacturing or in the final consumer package. Furthermore, the MOD value at 10% elongation corresponds to the film's ability to remain stiff rather than loosen and sag when in contact with liquid pouch contents. In particular, a film having a higher MOD value corresponds to a pouch that is less likely to soften and take on a loose, sagging appearance when in contact with liquid pouch contents containing low molecular weight polyol. In various embodiments, the third water-soluble film has a modulus of at least about 20, 21, 22, 23, 24, 25, or 27 N / mm. 2 , and / or up to about 24, 25, 27, 28, 29, or 30 N / mm 2 (For example, about 20N / mm 2 ~Approx. 30N / mm 2 , or about 20N / mm 2 ~about 28N / mm 2 , or about 22N / mm 2 ~Approx. 25N / mm 2 ) MOD value.

[0078] Preferably, the third water-soluble film comprises 0.1% to 3.5% by weight of the water-soluble film, or 0.1% to 2.5% by weight, or 1% to 2% by weight, or 0.5% to 2% by weight. Suitable surfactants can include nonionic, cationic, anionic, and zwitterionic classes. Suitable surfactants include, but are not limited to, nonionic surfactants, including but not limited to polyoxyethylenated polyoxypropylene glycols, alcohol ethoxylates, alkylphenol ethoxylates, tertiary acetylenic glycols, and alkanolamides; cationic surfactants, including but not limited to polyoxyethylenated amines, quaternary ammonium salts, and quaternized polyoxyethylenated amines; and zwitterionic surfactants, including but not limited to amine oxides, N-alkyl betaines, and sulfobetaines. For example, nonionic surfactants can be selected from alcohol ethoxylates, cationic surfactants can be selected from quaternary ammonium salts, and zwitterionic surfactants can be selected from amine oxides. Other suitable surfactants include dioctyl sodium sulfosuccinate, lactylated fatty acid esters of glycerol and propylene glycol, lactylic esters of fatty acids, sodium alkyl sulfates, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, lecithin, acetylated fatty acid esters of glycerol and propylene glycol, and acetylated esters of fatty acids, and combinations thereof.

[0079] Preferably, the third water-soluble film has a residual moisture content, as measured by Karl Fischer titration, of at least 4%, more preferably in the range of 4% to 15%, and even more preferably 5% to 10% by weight of the third water-soluble film.

[0080] Preferably, the third water-soluble film comprises one or more ingredients selected from the group consisting of plasticizers, plasticizer compatibilizers, lubricants, release agents, fillers, extenders, crosslinkers, antiblocking agents, antioxidants, detackifying agents, antifoaming agents, nanoparticles, bleaching agents, surfactants, and combinations thereof.

[0081] Preferably, the third water-soluble film comprises one or more plasticizers in an amount ranging from 5% to 50% by weight of the third water-soluble film, preferably 10% to 40% by weight, most preferably 20% to 30% by weight. Preferably, the plasticizer in the third water-soluble film is selected from a polyol, a sugar alcohol, or a mixture thereof, preferably, the polyol comprises a polyol selected from the group consisting of glycerol, diglycerin, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycols of 400 MW or less, neopentyl glycol, 1,2-propylene glycol, 1,3-propanediol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, and polyether polyols, or a mixture thereof, and the sugar alcohol comprises a sugar alcohol selected from the group consisting of isomalt, maltitol, sorbitol, xylitol, erythritol, adonitol, dulcitol, pentaerythritol, and mannitol, or a mixture thereof. Most preferably, the plasticizer is selected from the group consisting of sorbitol, glycerol, dipropylene glycol, polyethylene glycol, trimethylolpropane, and mixtures thereof.

[0082] Preferably, the third water-soluble film includes a lubricant / release agent. Suitable lubricants / release agents include, but are not limited to, fatty acids and their salts, fatty alcohols, fatty acid esters, fatty amines, fatty amine acetates, and fatty acid amides. Preferred lubricants / release agents are fatty acids, fatty acid salts, and fatty amine acetates. The amount of lubricant / release agent in the third water-soluble film ranges from 0.02% to 1.5% by weight, preferably 0.1% to 1% by weight, of the third water-soluble film.

[0083] Preferably, the third water-soluble film comprises a filler, a spreading agent, an antiblocking agent, a detackifying agent, or a mixture thereof. Suitable fillers, extenders, antiblocking agents, detackifying agents, or mixtures thereof include, but are not limited to, starch, modified starch, crosslinked polyvinylpyrrolidone, crosslinked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, and mica. Preferred materials are starch, modified starch, and silica. Preferably, the amount of the filler, spreading agent, antiblocking agent, detackifying agent, or mixtures thereof in the third water-soluble film ranges from 0.1% to 25% by weight of the third water-soluble film, preferably from 1% to 10% by weight, more preferably from 2% to 8% by weight, and most preferably from 3% to 5% by weight. In the absence of starch, one preferred range of suitable fillers, spreading agents, anti-tack agents, detackifying agents, or mixtures thereof is 0.1% to 1%, preferably 4%, more preferably 6%, even more preferably 1% to 4%, and most preferably 1% to 2.5% by weight of the third water-soluble film.

[0084] The third water-soluble film may comprise printed areas, which may be obtained using standard techniques such as flexographic printing or inkjet printing.

[0085] The first water-soluble film may include an aversive agent, such as a bitter agent. Suitable bitter agents include, but are not limited to, naringin, sucrose octaacetate, quinine hydrochloride, denatonium benzoate, or mixtures thereof. Any suitable concentration of the aversive agent may be used in the film. Suitable concentrations include, but are not limited to, 1-5000 ppm, or even 100-2500 ppm, or even 250-2000 ppm.

[0086] Preferably, the third water-soluble film and each individual component thereof independently contains between 0 ppm and 20 ppm, preferably between 0 ppm and 15 ppm, more preferably between 0 ppm and 10 ppm, even more preferably between 0 ppm and 5 ppm, even more preferably between 0 ppm and 1 ppm, even more preferably between 0 ppb and 100 ppb, and most preferably 0 ppb dioxane. Those skilled in the art will recognize known methods and techniques for determining dioxane levels within water-soluble films and their components.

[0087] Preferably, the first water-soluble film and the third water-soluble film are the same. By "same" herein is meant that the first water-soluble film and the third water-soluble film are physically and chemically identical prior to modification during unit dose article manufacturing, and by "same" is meant within standard processing to make specification changes.

[0088] Method for producing a water-soluble film The water-soluble film used in the water-soluble unit dose article of the film of the present disclosure can be manufactured by any suitable method. The process for manufacturing the water-soluble film includes solvent casting, blow molding, extrusion, or blown extrusion, as generally known in the art. The process for solvent casting is well known in the art. For example, in the film forming process, resin and secondary additives are dissolved in a solvent, typically water, which is metered onto a surface, and then substantially dried (or forced dried) to form a cast film, and then the resulting cast film is removed from the casting surface. This process can be carried out in batches, and is more efficiently carried out in a continuous process.

[0089] In the formation of a continuous film, it is conventional practice to meter a solution of the resin and secondary components onto a moving casting surface, such as a continuously moving metal drum or belt, allow the solvent to substantially remove from the liquid, thereby forming a self-supporting cast film, and then peel the resulting cast film from the casting surface. The solution can be optionally metered or coated onto a carrier film, release liner, or removable backing, so that after solvent removal, the resulting cast film or coating can be separated from the carrier film, release liner, or removable backing (e.g., immediately after drying or at a later time, e.g., before use), or can remain attached to the carrier film, release liner, or removable backing. The film or coating prepared on the carrier film, release liner, or removable backing can be self-supporting or non-self-supporting.

[0090] Generally, the amount of water in a metered solution of polyvinyl alcohol, additional resin, and / or secondary components for film casting is selected so that when the solution is heated to the casting temperature, the solution has a maximum solids level below the viscosity inflection point. Methods for determining the amount of solids at the viscosity inflection point are known in the art. Generally, the water content of the metered solution can include 60-85% water or 60-75% water to provide a solution suitable for casting with a typical casting solution. The viscosity of the casting solution can be, for example, at least about 20,000 cps at 185°F (85°C), at least 30,000 cps at 185°F (85°C), for example, about 40,000 cps to about 50,000 cps at 185°F (85°C).

[0091] The solution can be cast at any suitable temperature such that the film has a temperature during drying, for example, in the range of about 50° C. to about 105° C. While not intending to be bound by theory, it is believed that if the casting solution and film temperature drops below about 50° C., the amount of time required to dry the film increases unnecessarily and the length of the drying chamber required to completely dry the casting solution increases unnecessarily. Additionally, without intending to be bound by theory, it is believed that if the solution and film temperature increases above about 105° C., the solvent may rapidly boil out of the film, resulting in film surface defects such as holes or blisters in the finished film, and / or may promote undesirable reactions between adjacent PVOH backbones, resulting in a film with reduced solubility.

[0092] In a continuous or semi-continuous casting process, the moving casting surface can have a line speed ranging from about 5 m / min to about 50 m / min. The line speed can affect the properties of the resulting film, such as physical properties, thickness, residual moisture content, and film quality. In general, assuming that the solution delivery rate remains constant, as the line speed decreases, the resulting film thickness increases, and as the line speed increases, the resulting film thickness decreases. In general, as the line speed increases, the residence time of the film in the dryer decreases, thereby necessitating an increase in the drying temperature, which can lead to drying defects or adhesion at sufficiently high temperatures. In contrast, as the line speed decreases, the residence time of the film in the dryer increases.

[0093] Any of the first, second, third, or additional films according to the disclosure herein may be produced by solvent casting, for example, using a solvent band casting system. The system may include a tank for mixing and / or storing the polymer solution with any secondary additives for use with a band casting machine having at least first and second rotating drums, around which a continuous band (e.g., a metal band) is tensioned to move with the rotation of the drums. A sheeting die may apply the polymer solution from the tank to the metal band, and a drying chamber enclosing at least a portion of the metal band below the sheeting die is used to remove the solvent from the polymer solution as it moves in a thin sheet over the metal band. Additionally, a release coating may be used to provide one or more benefits to the film and / or process. For example, a release coating may substantially reduce or eliminate air bubbles in the produced polymer film, or a release coating may improve the ease of release of the produced film from the casting surface. A roll coater release coating applicator in communication with a supply of release coating and a portion of the band can transfer a fluid release coating to the casting surface prior to application of the polymer solution to the band. Suitable solvent band casting systems and associated materials are further described in U.S. Patent Application Publication No. 2006 / 0081176 A1, the disclosure of which is incorporated herein by reference in its entirety.

[0094] In general, the casting surface can be any suitable substrate for producing polymeric films to one skilled in the art. In an embodiment, the substrate can be a casting roller or drum, a casting belt, or a combination thereof. As used herein, a substrate is used to produce a polymeric film from a polymeric resin or a polymeric resin solution. The substrate comprises a substrate surface, the substrate surface being coated with a release coating. The polymeric resin solution can be cast onto the substrate while the substrate is moving, e.g., rotating. In an embodiment, the substrate is a casting drum. In an embodiment, the substrate is a casting belt. The substrate can comprise stainless steel, and can optionally have a stainless steel surface. The substrate can comprise stainless steel, which is optionally plated, e.g., chrome-plated, nickel-plated, zinc-plated, or a combination thereof.

[0095] In general, the release coating may include one or more surfactants and an optional carrier (e.g., water). The release coating may include one or more surfactants selected from, for example, fluorosurfactants, non-fluorinated anionic surfactants, non-fluorinated zwitterionic surfactants, salts thereof, or any combination thereof. In embodiments, the anionic or zwitterionic surfactant may be non-fluorinated and may be selected from the group consisting of C6-C 30 Phosphate esters, C6-C 30 Phosphate diesters, C6-C 30 Carboxylate, C6-C 30 Dicarboxylates, C6-C 30 Sulfate, C6~C 30 In embodiments, the release coating comprises a non-fluorinated zwitterionic surfactant or a salt thereof. In embodiments, the release coating comprises a non-fluorinated anionic surfactant or a salt thereof. In some embodiments, the non-fluorinated anionic surfactant is a C6-C 30 Phosphate ester or C8~C 16 Phosphate esters, C6-C 60Phosphate diester, C 16 ~C 32 Phosphate diesters, C6-C 30 Carboxylate, C6-C 30 Dicarboxylates, C6-C 30 Sulfate, C6~C 30 In some embodiments, the non-fluorinated anionic surfactant comprises a C6-C disulfate, a C6-C disulfate, or a salt thereof. 30 Phosphate ester or C6~C 18 Phosphate esters, C6-C 60 Phosphate diester, C 18 ~C 32 Phosphate diesters, or salts thereof. In embodiments, the anionic surfactant may be selected from one or more of C6-based ammonium fluoroaliphatic phosphate esters; tridecyl alcohol ethoxylate phosphate esters, POE-12; tridecyl alcohol ethoxylate phosphate esters, POE-3; laureth-11 carboxylic acid; crypto-anionic surfactants-laureth-6 carboxylic acid; or sodium lauryl ether sulfate, POE-4.

[0096] As used herein, the term "non-fluorinated" refers to surfactants having less than 0.01% fluorine by weight based on the total molecular weight of the compound, or less than 0.001% fluorine by weight based on the total molecular weight of the compound, or less than 0.0001% fluorine by weight based on the total molecular weight of the compound.

[0097] In an embodiment, the release coating can include a fluorosurfactant, such as a perfluoroalkyl-containing compound. In an embodiment, the fluorosurfactant can include a solution of ZONYL FSP surfactant (EI du Pont de Nemours and Company). A range of about 0.05% to about 5.0% by weight of surfactant in the release coating is contemplated. The amount of surfactant required to provide sufficient wetting can vary depending on the film coated on the band. Other products may require higher concentrations to improve release properties. Extended wetting of hard surfaces becomes more efficient with higher surfactant concentrations until the surfactant solution reaches a critical micelle concentration (CMC). This concentration represents a threshold beyond which additional surfactant provides no further efficiency in extended wetting. However, increasing the concentration beyond the CMC can improve wetting with the polymer solution and improve the release properties of some film formulations.

[0098] The release coating may be applied to the surface of a substrate and may optionally be subsequently dried prior to casting the polymeric resin or polymeric resin solution onto the surface-coated substrate. In embodiments, the release coating may have a pH of about 1 to about 5 when applied to the surface of a substrate prior to drying the release coating on the surface of the substrate. In embodiments in which the surfactant comprises a non-fluorinated anionic surfactant, a non-fluorinated zwitterionic surfactant, salts thereof, and combinations thereof, the release coating may have a pH of about 1 to about 8 or a pH of about 1 to about 5 when applied to the surface of a substrate prior to drying the release coating on the surface of the substrate. For example, the release coating may have a pH of about 1, about 1.5, about 2, about 2.5, about 3, about 3.5, about 4, about 5, about 6, about 7, or about 8 when applied to the surface of a substrate. In embodiments, the release coating may have a pH of from about 1 to about 7, or from about 1 to about 6, or from about 1 to about 4, or from about 1 to about 3, or from about 2 to about 7, or from about 2 to about 6, or from about 2 to about 5, or from about 2 to about 4, or from about 2 to about 3, or from about 3 to about 7, or from about 3 to about 5, or from about 1.5 to about 3.5, or from about 4 to about 7 when applied to the surface of the substrate prior to drying the release coating on the surface of the substrate.

[0099] In embodiments, the release coating can have a surfactant concentration in the range of about 0.001% to about 100% by weight, based on the total weight of the release coating. In embodiments, the release coating can have a surfactant concentration in the range of about 0.001% to about 20% by weight, prior to drying the release coating on the surface of the substrate. For example, the release coating can have a surfactant concentration in the range of about 0.001% to about 10% by weight, or about 0.01% to about 5% by weight, or about 0.01% to about 4% by weight, or about 0.01% to about 3% by weight, or about 0.01% to about 2% by weight, or about 0.05% to about 2% by weight, or about 0.1% to about 2% by weight, or about 0.5% to about 2% by weight, prior to drying the release coating on the surface of the substrate. In embodiments, the release coating may have a surfactant concentration in the range of about 0.01% to about 4.00% by weight, based on the total weight of the release coating, prior to drying the release coating on the surface of the substrate. In embodiments, the release coating may have a surfactant concentration in the range of about 0.05% to about 2.00% by weight, based on the total weight of the release coating, prior to drying the release coating on the surface of the substrate. In embodiments, the release coating may have a surfactant concentration in the range of about 2.5% to about 100% by weight, based on the total weight of the release coating, prior to drying the release coating on the surface of the substrate. For example, after drying the release coating on the surface of the substrate, the release coating can have a surfactant concentration in the range of about 3% to about 100% by weight, or about 4% to about 90% by weight, or about 4% to about 80% by weight, or about 4% to about 70% by weight, or about 4% to about 50% by weight, or about 4% to about 30% by weight, or about 4% to about 20% by weight, or about 4.7% to about 100% by weight, or about 5% to about 90% by weight, based on the total weight of the release coating. In an embodiment, the release coating can have a surfactant concentration in the range of about 4.7% to about 100% by weight, based on the total weight of the release coating, after drying the release coating on the surface of the substrate.For example, the release coating may include a ZONYL surfactant in an amount ranging from about 0.05% to about 5.0% by weight, based on the total weight of the release coating.

[0100] Generally, the release coatings described herein may have a hydrophilic-lipophilic balance in the range of about 1 to about 30. In embodiments, the release coatings may have a hydrophilic-lipophilic balance in the range of about 1 to about 20, or about 1 to about 18, or about 1 to about 17, or about 1 to about 16, or about 1 to about 15, or about 2 to about 17, or about 3 to about 17, or about 4 to about 15, or about 5 to about 12, or about 8 to about 12. In embodiments, the release coatings may have a hydrophilic-lipophilic balance in the range of about 1 to about 20. In embodiments, the release coatings may have a hydrophilic-lipophilic balance in the range of about 3 to about 17.

[0101] Typically, the release coating has a thickness of about 0.1 nm to about 100 nm on the surface of the substrate. In embodiments, the release coating can have a thickness of about 0.1 nm to about 80 nm, or about 0.1 nm to about 60 nm, or about 0.1 nm to about 40 nm, or about 0.1 nm to about 40 nm, or about 0.1 nm to about 20 nm, or about 0.1 nm to about 10 nm, or about 1 nm to about 10 nm, or about 1 nm to about 5 nm on the surface of the substrate. In embodiments, the release coating has a thickness of about 0.1 nm to about 40 nm on the surface of the substrate. In embodiments, the release coating has a thickness of about 0.1 nm to about 10 nm on the surface of the substrate.

[0102] Household care compositions The water soluble unit dose article comprises a household care composition.

[0103] The household care composition is preferably selected from the group consisting of light duty liquid detergent compositions, heavy duty liquid detergent compositions, hard surface cleaning compositions, laundry detergent gels, bleaching compositions, laundry additives, fabric softener compositions, shampoos, body washes, other personal care compositions, and mixtures thereof, preferably liquid laundry detergent compositions.

[0104] The term "liquid laundry detergent composition" refers to any laundry detergent composition that contains a liquid capable of wetting and treating fabrics, including, but not limited to, liquids, gels, pastes, dispersions, etc. A liquid composition may include solids or gases in any suitable finely divided form, but liquid compositions exclude generally non-flowable forms such as tablets or granules.

[0105] The liquid detergent compositions may be used in hand washing fabric operations or in fabric washing operations in an automatic washing machine.

[0106] Preferably the liquid laundry detergent composition comprises from 15% to 55% non-soap anionic surfactant by weight of the laundry detergent composition. Preferably the detergent composition comprises from 20% to 55%, more preferably from 25% to 50% non-soap anionic surfactant.

[0107] Preferably, the non-soap anionic surfactant comprises a linear alkyl benzene sulfonate. Preferably, the linear alkyl benzene sulfonate is C 10 ~C 16 Alkylbenzene sulfonate, C 11 ~C 14 Preferably, the alkylbenzene sulfonate is an amine neutralized alkylbenzene sulfonate, an alkali metal neutralized alkylbenzene sulfonate, or a mixture thereof. The amine may preferably be selected from monoethanolamine, triethanolamine, or a mixture thereof. The alkali metal may preferably be selected from sodium, potassium, magnesium, or a mixture thereof. Preferably, the liquid laundry detergent composition comprises from 1% to 40%, preferably from 3% to 40%, more preferably from 6% to 35% by weight of the liquid laundry detergent composition of linear alkylbenzene sulfonate.

[0108] Preferably, the non-soap anionic surfactant comprises an alkyl sulfate anionic surfactant, the alkyl sulfate anionic surfactant being selected from alkyl sulfate, alkoxylated alkyl sulfate, or mixtures thereof. The alkyl sulfate anionic surfactant may be a primary or secondary alkyl sulfate anionic surfactant, or mixtures thereof, preferably a primary alkyl sulfate anionic surfactant. Preferably, the alkoxylated alkyl sulfate comprises an ethoxylated alkyl sulfate, a propoxylated alkyl sulfate, a mixed ethoxylated / propoxylated alkyl sulfate, or mixtures thereof, more preferably an ethoxylated alkyl sulfate. Preferably, the ethoxylated alkyl sulfate has an average degree of ethoxylation of 0.1-5, preferably 0.5-3. Preferably, the ethoxylated alkyl sulfate has an average alkyl chain length of 8-18, more preferably 10-16, most preferably 12-15. Preferably, the alkyl chain of the alkyl sulfate anionic surfactant may be linear, branched, or a mixture thereof. Preferably, the branched alkyl sulfate anionic surfactant is a branched primary alkyl sulfate, a branched secondary alkyl sulfate, or a mixture thereof, preferably a branched primary alkyl sulfate, and the branching is preferably at the 2-position or may be further down the alkyl chain or may be multi-branched with the branching extending up the alkyl chain. The weight average degree of polymerization of the alkyl sulfate anionic surfactant may be 0% to 100%, preferably 0% to 95%, more preferably 0% to 60%, and most preferably 0% to 20%. Alternatively, the weight average degree of polymerization of the alkyl sulfate anionic surfactant may be 70% to 100%, preferably 80% to 90%. Preferably, the alkyl chain is selected from naturally derived materials, synthetically derived materials, or a mixture thereof. Preferably, the synthetically derived material comprises an oxo synthetic material, a Ziegler synthetic material, a Guerbet synthetic material, a Fischer-Tropsch synthetic material, an iso-alkyl synthetic material, or mixtures thereof, preferably an oxo synthetic material.Preferably the liquid laundry detergent composition comprises from 1% to 35%, preferably from 3% to 30%, more preferably from 6% to 20% alkyl sulphate anionic surfactant by weight of the liquid laundry detergent composition.

[0109] Preferably, the non-soap anionic surfactant comprises a linear alkylbenzene sulfonate and an alkoxylated alkyl sulfate, more preferably the weight ratio of the linear alkylbenzene sulfonate to the alkoxylated alkyl sulfate is from 1:2 to 9:1, preferably from 1:1 to 7:1, more preferably from 1:1 to 5:1, most preferably from 1:1 to 4:1.

[0110] The liquid laundry detergent composition comprises from 2.5% to 30% by weight of the liquid laundry detergent composition of a nonionic surfactant, which is described in more detail below.

[0111] Preferably, the weight ratio of the non-soap anionic surfactant to the nonionic surfactant is from 1:1 to 13:1, preferably from 1.25:1 to 10:1, more preferably from 1.5:1 to 7.5:1.

[0112] Preferably, the liquid laundry detergent composition comprises a nonionic surfactant. Preferably, the nonionic surfactant comprises an alkoxylated alcohol, and the alkoxylated alcohol is derived from a synthetic alcohol, a natural alcohol, or a mixture thereof. The alkoxylated alcohol can be a primary alkoxylated alcohol, a secondary alkoxylated alcohol, or a mixture thereof, preferably a primary alkoxylated alcohol. Preferably, the alkoxylated alcohol comprises an ethoxylated alcohol, a propoxylated alcohol, a mixed ethoxylated / propoxylated alcohol, or a mixture thereof, more preferably an ethoxylated alcohol. Alternatively, the alkoxylated alcohol can also comprise a higher alkoxy group, such as a butoxy group. In the case of a mixed alkoxy group, the alkoxy groups can be randomly arranged or present in blocks, preferably present in blocks. For example, the mixed ethoxy (EO) / propoxy (PO) group can be arranged in an EO / PO block, a PO / EO block, an EO / PO / EO block, or a PO / EO / PO block. Preferably, the ethoxylated alcohol has an average degree of ethoxylation of 0.1-20, preferably 5-15, most preferably 6-10. If propoxylation is present, preferably the average degree of propoxylation is 0.1-25, more preferably 2-20, most preferably 5-10. Preferably, the alkoxylated, preferably ethoxylated, alcohol has an average alkyl chain length of 8-18, more preferably 10-16, most preferably 12-15. Preferably, the alkyl chain of the alkoxylated alcohol is linear, branched, or a mixture thereof, and the branched alkoxylated alcohol is a branched primary alkoxylated alcohol, a branched secondary alkoxylated alcohol, or a mixture thereof, preferably a branched primary alkoxylated alcohol. Preferably, the weight average degree of polymerization of the alkoxylated alcohol is 0%-100%, preferably 0%-95%, more preferably 0%-60%, most preferably 0%-20%. The branches may be at the 2-alkyl position, or further down the alkyl chain, or may be multi-branched with individual branches extending up the alkyl chain.Preferably, the synthetically derived material comprises an oxo synthetic material, a Ziegler synthetic material, a Guerbet synthetic material, a Fischer-Tropsch synthetic material, an iso-alkyl branched material, or mixtures thereof, preferably an oxo synthetic material. Preferably, the liquid laundry detergent composition comprises from 0.5% to 20%, preferably from 1% to 15%, more preferably from 3% to 12%, by weight of the liquid laundry detergent composition of a non-ionic surfactant, preferably the non-ionic surfactant comprises an alkoxylated alcohol. Without wishing to be bound by theory, it is believed that non-ionic surfactants, particularly alkoxylated alcohol non-ionic surfactants, provide superior body soil cleaning and soil suspension benefits.

[0113] Preferably, the weight ratio of non-soap anionic surfactant to nonionic surfactant is from 1:1 to 20:1, from 1.5:1 to 17.5:1, from 2:1 to 15:1, or from 2.5:1 to 13:1.

[0114] Preferably the liquid laundry detergent composition comprises a fatty acid, preferably a neutralized fatty acid soap, preferably a fatty acid salt, more preferably an amine neutralized fatty acid salt, preferably the amine is an alkanolamine, more preferably selected from monoethanolamine, diethanolamine, triethanolamine, or mixtures thereof, more preferably monoethanolamine. The liquid detergent composition may comprise from 1.5% to 20%, from 2% to 15%, from 3% to 12%, or from 4% to 10% fatty acid by weight of the liquid detergent composition.

[0115] Preferably the liquid laundry detergent composition comprises from 1% to 20%, preferably from 5% to 15% water by weight of the liquid laundry detergent composition.

[0116] Preferably the liquid laundry detergent composition comprises from 10% to 40%, preferably from 15% to 30% by weight of the liquid laundry detergent composition of a non-aqueous solvent, preferably the non-aqueous solvent is selected from 1,2-propanediol, dipropylene glycol, tripropylene glycol, glycerol, sorbitol, polyethylene glycol or mixtures thereof.

[0117] Preferably, the liquid laundry detergent composition comprises adjunct ingredients selected from the group comprising builders, perfumes, enzymes, citrates, bleaches, bleach catalysts, dyes, hueing dyes, brighteners, cleaning polymers including alkoxylated polyamines and polyethyleneimines, soil release polymers, fabric care polymers including cationic hydroxyethylcellulose and cationic polyglucans, surfactants, solvents, dye transfer inhibitors, chelating agents, encapsulated perfumes, polycarboxylates, structurants, pH adjusters, antioxidants including Ralox 35, and mixtures thereof.

[0118] Preferably, the laundry detergent composition comprises a further enzyme selected from the group comprising hemicellulase, peroxidase, protease, cellulase, xylanase, lipase, phospholipase, esterase, cutinase, pectinase, keratanase, reductase, oxidase, phenoloxidase, lipoxygenase, ligninase, pullulanase, tannase, pentosanase, malanase, β-glucanase, arabinosidase, hyaluronidase, chondroitinase, laccase, xyloglucanase, mannanase and amylase, nuclease or mixtures thereof, preferably selected from the group comprising protease, amylase, cellulase, lipase, xyloglucanase, mannanase and mixtures thereof. Preferably, the further enzyme is a lipase.

[0119] As used herein, the term lipase includes enzymes that catalyze the hydrolysis of fats (lipids). Lipases are a subclass of esterases. Lipases suitable for the present invention include phospholipases, acyltransferases or perhydrolases, such as acyltransferases with homology to Candida antarctica lipase A, acyltransferases from Mycobacterium smegmatis, perhydrolases from the CE7 family, and variants of M. smegmatis perhydrolase, in particular the S54V variant used in the commercial product Gentle Power Bleach from Huntsman Textile Effects Pte Ltd. Suitable lipases and cutinases include those of bacterial or fungal origin. Chemically modified or protein engineered mutant enzymes are included. Examples include lipases from Thermomyces species, e.g., T. lanuginosus (previously named Humicola lanuginosa), cutinases from Humicola species, e.g., H. insolens, lipases from strains of the genus Pseudomonas (some of which have now been renamed Burkholderia), e.g., P. alcaligenes or P. pseudoalcaligenes, P. cepacia, Pseudomonas strain SD705, P. wisconsinensis, GDSL-type Streptomyces lipases, cutinases from Magnaporthe grisea, cutinases from Pseudomonas mendocina, cutinases from Thermobifida fusca, and the like. Examples of lipases that can be used include lipases from Bacillus fusca, Geobacillus stearothermophilus lipase, Bacillus subtilis lipase, and lipases from Streptomyces griseus and S. pristinaespiralis.Typically, the lipase enzyme is present in the composition in an amount of enzymatically active protein of 0.001% to 0.03%, preferably 0.0025% to 0.025%, more preferably 0.005% to 0.02% by weight of the composition. Without wishing to be bound by theory, the enzyme is supplied as a preparation comprising the enzyme and other ingredients. The enzyme itself is a protein that catalyzes a reaction. By enzymatically active protein is meant herein an enzyme that is capable of actively catalyzing the relevant reaction.

[0120] Preferably the liquid laundry detergent composition has a pH of from 6 to 10, more preferably from 6.5 to 8.9, most preferably from 7 to 8, the pH of the laundry detergent composition being measured as a 10% product concentration in deionised water at 20°C.

[0121] The liquid laundry detergent composition may be Newtonian or non-Newtonian. Preferably, the liquid laundry detergent composition is non-Newtonian. Without wishing to be bound by theory, non-Newtonian liquids have different properties than Newtonian liquids, more specifically, the viscosity of non-Newtonian liquids depends on shear rate, while Newtonian liquids have a constant viscosity regardless of the applied shear rate. It is believed that the decrease in viscosity of non-Newtonian liquids upon application of shear further promotes the dissolution of the liquid detergent. The liquid laundry detergent composition described herein may have any suitable viscosity, depending on factors such as the formulated ingredients and the purpose of the composition.

[0122] Process for producing water-soluble unit dose articles A further aspect of the invention is a process for producing a water soluble unit dose article according to the invention, comprising the steps of: a. deforming a first water-soluble film in a mold via thermoforming, vacuum forming, or a combination thereof to create an open cavity; b. filling the open cavity with a household care composition; c. closing the filled open cavity with a second water-soluble film; and d. sealing the first water-soluble film and the second water-soluble film to create a closed intermediate, preferably the first water-soluble film and the second water-soluble film are sealed via solvent sealing, more preferably a solvent sealing solution is applied to the second side of the second water-soluble film, such that the second side of the second water-soluble film faces the first water-soluble film, prior to sealing the films together.

[0123] Alternatively, when a third water-soluble film is present, the process comprises: a. deforming a first water-soluble film in a mold via thermoforming, vacuum forming, or a combination thereof to create an open cavity; b. filling the open cavity with a household care composition; c. individually deforming the third water-soluble film in a mold via thermoforming, vacuum forming, or a combination thereof to create at least one open cavity; d. filling at least one open cavity from step c with a household care composition; e. closing the filled open cavity from step c with a second water-soluble film; f. sealing the second water-soluble film and the third water-soluble film to create a closed intermediate, preferably the second water-soluble film and the third water-soluble film are sealed via a solvent seal, more preferably a solvent sealing solution is applied to a first side of the second water-soluble film, the first side facing the third water-soluble film, prior to sealing the films together; g. closing the filled open cavity from step b with the closing intermediate from step f; h. sealing the first water-soluble film and the second water-soluble film to create a water-soluble unit dose article, preferably the first water-soluble film and the second water-soluble film are sealed via a solvent seal, more preferably a solvent sealing solution is applied to a second side of the second water-soluble film, the second side facing the first water-soluble film, prior to sealing the films together.

[0124] Preferably, the first water-soluble film in step a and the second water-soluble film in step c are identical before modification. By "same" herein is meant that the first water-soluble film and the third water-soluble film are physically and chemically identical before modification during unit dose article manufacturing, and by "same" is meant within the standard process of making specification changes.

[0125] The process for producing the water soluble unit dose articles can be an automated manufacturing process, such as a conveyor belt, a series of conveyor belts, a drum, a series of drums, or a combination thereof. Alternatively, the process for producing the water soluble unit dose articles can be a manual manufacturing line, where one or more sequences or steps are performed manually. Most preferably, the process is an automated process.

[0126] Preferably, the process for producing the water soluble unit dose articles is a continuous process. Alternatively, the process for producing the water soluble unit dose articles may be an intermittent or batch process. Preferably, the process for producing the water soluble unit dose articles is a continuous manufacturing process.

[0127] Preferably, the closed intermediate is produced on a rotating drum or a horizontal belt, preferably on a rotating drum. Preferably, the filled open cavities in steps a and b are produced on a horizontal belt or a rotating drum, preferably on a horizontal belt. If a rotating drum is used, the water-soluble film is preferably kept in place by a vacuum. If a horizontal belt is used, the water-soluble film is preferably kept in place by a vacuum.

[0128] Preferably, a plurality of unit dose articles are formed that are connected to each other by flat areas. Without wishing to be bound by theory, such a process involves manufacturing a plurality of water-soluble unit dose articles that are joined together by a non-deformable film to create a water-soluble web of unit dose articles. The non-deformable film is the flat area of ​​the water-soluble web between the unit dose articles. Thus, the flat area can include two or more water-soluble films sealed together.

[0129] The resulting web of water-soluble unit dose articles connected through the flat area is then transferred to a cutting station and cut to produce individual unit dose articles. Preferably, the cutting station cuts the web in the machine direction and cross direction. Preferably, the cutting is accomplished using a rotary knife. It may also be preferred that the cutting is done in a continuous manner, preferably at a constant line speed, and preferably while in a horizontal position. The cutting device may be, for example, a sharp article, or a hot article, or a laser, in the latter case, the hot article or laser "burns through" the film / sealed area. The cutting may be performed by one or more rotary knives. Preferably, the cutting is performed by one or more rotary knives, which cut in the machine direction, cross direction, or a combination thereof. Preferably, the rotary knives rotate at variable rotation speeds.

[0130] The solvent sealing solution may be applied by any suitable method, including contact and / or non-contact methods. For example, the solvent solution may be applied in a contact transfer process, for example, using a contact member comprising a non-absorbent or substantially impermeable material, for example, using an anilox roller, a rubber (e.g., EPDM) roller, or any combination thereof, optionally in combination with a doctor blade. The sealing solution may be applied using a drawdown bar, a Mayer bar, or a similar device. In another type of embodiment, the sealing solution may be applied using a contact member comprising an absorbent material, for example, natural felt, synthetic felt, porous plastic, foam, sponge, microfiber, cotton, polyester, extruded polyester fibers, nonwoven webs, etc., for example, in the form of a pad or roller. Application of the solvent sealing solution via a felt roll is specifically contemplated. The solvent sealing solution may be applied via a felt roll, a spray nozzle or a pour nozzle, or a combination thereof, preferably via a felt roll. Preferably, the solvent sealing solution comprises an aqueous solvent, a non-aqueous solvent, or a mixture thereof. Even more preferably, the solvent sealing solution comprises water. Preferably, the solvent sealing solution comprises at least 95% by weight of the solvent sealing solution, or even at least 98% by weight, or even at least 99% by weight, or even 100% by weight of water. Preferably, the solvent sealing solution is applied via a felt roll, via a spray nozzle or a pour nozzle, or a combination thereof, more preferably via a felt roll. Preferably, the solvent sealing solution is applied to the second water-soluble film. Preferably, the solvent sealing solution is present on the water-soluble film at 1 g to 30 g of sealing solution water per square meter, preferably 5 g to 20 g of sealing solution per square meter.

[0131] The water-soluble film may be preheated prior to deformation via a hot plate, infrared lamps, or a combination thereof, preferably infrared lamps.

[0132] The molds in which the articles can be manufactured can have any shape, length, width, and depth depending on the pouch dimensions required. The molds can also vary in size and shape, if desired. For example, the volume of the final unit dose article can be about 5 mL to about 300 mL, about 10 to 150 mL, or about 20 to about 100 mL, and the size of the molds adjusted accordingly.

[0133] Dimensions and values ​​disclosed herein should not be understood as being strictly limited to the exact numerical values ​​recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm." EXAMPLES

[0134] The effect of the presence versus absence of anionic polyvinyl alcohol copolymers, as well as the effect of different average molecular weights, expressed as 4% viscosity of aqueous polymer solutions (deionized water), of polyvinyl alcohol homopolymer blends within polyvinyl alcohol blends with polymer resins, was studied on 1) the susceptibility of the corresponding water-soluble films to create a foam layer on the film surface upon sealing solvent application, 2) the resulting sealing and unit dose article strength, and 3) the film / unit dose article dissolution profile.

[0135] Test materials: Water-soluble film: Solvent cast water-soluble test films differing monovariably in the selection of polyvinyl alcohol types were provided by MonoSol. The test films contained 65% water-soluble polyvinyl alcohol resin, the remainder being water, plasticizers, surfactants, and other materials typically present in water-soluble films. Comparative Examples 1-4 contained 15%-30% anionic copolymer by weight of the polyvinyl alcohol polymer resin, and as such are outside the scope of the present invention. Comparative Examples 5-7 contained polyvinyl alcohol homopolymer blends, but the average viscosities are outside the scope of the present invention.

[0136] Inventive Example 1 includes a polyvinyl alcohol homopolymer blend having an average viscosity according to the present invention. Resins containing anionic polyvinyl alcohol copolymers (% by weight of polyvinyl alcohol polymer resin): Comparative Example 1: Polyvinyl alcohol blend containing 70% polyvinyl alcohol homopolymer (13 mPa.s, dH 86%) - 30% methyl maleate based anionic polyvinyl alcohol copolymer (4% anionic substitution, 18 mPa.s, 90% dH). Comparative Example 2: Polyvinyl alcohol blend containing 85% polyvinyl alcohol homopolymer (13 mPa.s, dH 86%) - 15% methyl maleate based anionic polyvinyl alcohol copolymer (4% anionic substitution, 18 mPa.s, 90% dH). Comparative Example 3: Polyvinyl alcohol blend containing 85% polyvinyl alcohol homopolymer (8 mPa.s, dH 88%) - 15% methyl maleate based anionic polyvinyl alcohol copolymer (4% anionic substitution, 18 mPa.s, 90% dH). Comparative Example 4: Polyvinyl alcohol blend containing 85% polyvinyl alcohol homopolymer (18 mPa.s, dH 88%) - 15% methyl maleate based anionic polyvinyl alcohol copolymer (4% anionic substitution, 18 mPa.s, 90% dH). Resin made of polyvinyl alcohol homopolymer (weight % of polyvinyl alcohol polymer resin): Comparative Example 5: 100% polyvinyl alcohol homopolymer (13 mPa.s, dH 86%). Comparative Example 6: Polyvinyl alcohol homopolymer blend containing 80% polyvinyl alcohol homopolymer (13 mPa.s, dH 86%) - 20% polyvinyl alcohol homopolymer (8 mPa.s, dH 88%) - average viscosity: 12 mPa.s. Comparative Example 7: Polyvinyl alcohol homopolymer blend containing 80% polyvinyl alcohol homopolymer (13 mPa.s, dH 86%) - 20% polyvinyl alcohol homopolymer (18 mPa.s, dH 88%) - average viscosity: 14 mPa.s. Inventive Example 1: Polyvinyl alcohol homopolymer blend containing 60% Polyvinyl alcohol homopolymer (13 mPa.s, dH 86%) - 40% Polyvinyl alcohol homopolymer (8 mPa.s, dH 88%) - Average viscosity: 11 mPa.s.

[0137] Water-soluble unit dose articles: These water-soluble test films were used to make water-soluble unit dose articles. A first water-soluble film, comprising a polyvinyl alcohol blend comprising 60% polyvinyl alcohol homopolymer (23 mPa.s, dH 87%) and 40% methyl maleate-based anionic polyvinyl alcohol copolymer (4% anionic substitution, 18 mPa.s, 90% dH) provided by MonoSol, was drawn into a mold containing two side-by-side cavities under the influence of vacuum to make open compartments. The detergent composition was injected inside these open compartments, and the filled open compartments were then closed with the above test film. The side-by-side configuration represents the top compartment configuration, as shown in Figure 1. The two films were sealed together with water, and the sealing water was pre-applied onto the test film through a pre-wetted felt roll on the surface facing the first water-soluble film. The target sealing water coat weight was 9 grams of water per square meter of water-soluble film. A third water-soluble film of the same composition as the first water-soluble film was drawn into a separate mold containing a single cavity under the influence of vacuum to create an open compartment. Before closing the open compartment with the side-by-side compartment unit dose article created above, a detergent composition was injected into the open compartment to create a water-soluble unit dose article as shown in Figure 1 and sold under the brand Fairy NonBio by Procter and Gamble in the UK in July 2020. For this, sealing water was pre-applied on the test film through a pre-wetted felt roll on the surface facing the third water-soluble film. The target sealing water coat weight was 13 grams of water per square meter of water-soluble film. All water-soluble films used had a starting thickness of 76 microns before article creation.

[0138] Detergent Composition: The respective detergent compositions added to the individual compartments described in the Water-Soluble Unit Dose Article section above are summarized in Table 1. The detergent compositions were prepared by mixing the individual components in a batch process.

[0139] [Table 1] * An ethoxylated polyethyleneimine having a polyethyleneimine backbone with an average degree of ethoxylation of 20 per EO chain and a MW of approximately 600. ** Lutensit Z96: A partially sulfated polyethoxylated hexamethylenediamine available from BASF. *** Premix composition: 37% by weight cationic hydroxyethyl cellulose, 60% by weight PPG 400, 3% by weight Acusol 880 - premix ingredients reflected in formulation composition above

[0140] Test results: With vs. without foam layer: The water-soluble test films according to the present invention and water-soluble test films outside the scope of the present invention were visually evaluated for the presence versus absence of a foam layer created on the water-soluble film surface after the sealing water application step on the test film before contacting with the third water-soluble film. The results summarized in Table 2 below clearly show that the water-soluble films containing water-soluble resins containing 15-30% anionic copolymers (Comparative Examples 1-4) are sensitive to creating a foam layer on the surface of the water-soluble film during sealing water application, in contrast to the water-soluble films containing polymer resins consisting of polyvinyl alcohol homopolymers (blends) (Inventive Example 1 and Comparative Examples 5-7). It is believed that this foam layer causes uneven spreading of the sealing water and accordingly leads to poor sealing quality behind the presence of weak sealing spots.

[0141] [Table 2]

[0142] Pouch strength pass rate % and seal failure rate %: Test Method: This test method describes the implementation to determine pouch strength pass % and seal failure % using Mark-10 test equipment ESM750SLCE (jjbos bv, Marconistraat 1, NL-2809 PH Gouda, The Netherlands) with a load cell up to 100 kN (kilonewtons). Under the influence of an external compressive force, the pouch deforms and exerts stress on both the film and the sealed area. The internal pressure within the pouch depends on the externally applied force across the pouch surface area. Pouch strength (Newton) is defined as the maximum compressive force required by two parallel plates to increase the internal pressure of the pouch to the point of bursting. Pouches that burst at the sealed area are reported as "seal failure" which is used in the calculation of the seal failure % (seal failure = 1, no seal failure = 0) over 18 replicates. Pouches that burst at a pressure equivalent to that produced by compression of less than 300 N are reported as "fails" which are used in the calculation of pouch strength pass % (fail = 0, pass = 1) over 18 replicates.

[0143] The pouch strength pass percentage and seal failure percentage were determined after storing the water-soluble pouches at ambient conditions for 7 days and preconditioning at 23°C / 50% RH for 16-24 hours. The method is performed in an indoor environment with 40-50% relative humidity (RH) and 22-24°C. The water-soluble pouches are tested within 1 hour of removal from preconditioning.

[0144] FIG. 2 shows a schematic diagram of the basic setup of the pouch strength pass rate % and seal failure % test. To measure the pouch strength pass rate % and seal failure %, the pouch 510 is enclosed in a resulting sealed plastic bag 500 (150 mm x 124 mm with closure, 60 micron thickness, e.g. Raja grip RGP6B) to prevent contamination of the working environment due to pouch breakage. The pouch 510 is centered within the bag and placed between the two compression plates 520, 530 of the instrument. The pouch 510 is placed in an upright position such that the width seal dimension 540 (e.g. the smallest dimension in a defined rectangular plane that just encompasses the seal area, 41 mm for the actual pouch tested) is between the compression plates (x direction) so that stress is applied to the width seal. Therefore, the diameter of the compression plates needs to be large enough to not pinch the pouch as it deforms (here D=116 mm). During compression, the rate of decrease in the distance between plates 520 and 530 is set at 200 mm / min. Eighteen replicates are performed for each test group, and pouch strength % pass and % seal failure data across these 18 replicates are reported.

[0145] Test results: The results summarized in Table 3 clearly show that the water-soluble unit dose article comprising a water-soluble test film comprising a polyvinyl alcohol-based polymer resin comprised of a homopolymer blend having an average viscosity profile according to the present invention (Invention Example 1) has superior pouch strength and seal failure profile compared to the water-soluble unit dose articles comprising a water-soluble test film comprising a polyvinyl alcohol-based polymer resin comprised of a homopolymer blend having an average viscosity profile outside the range of the present invention (Comparative Examples 5-7), and compared to the water-soluble unit dose articles comprising a water-soluble test film comprising a polyvinyl alcohol-based polymer resin comprising 15%-30% anionic polyvinyl alcohol copolymer (Comparative Examples 1-4).

[0146] [Table 3] * Higher is better **Lower is better

[0147] Water-soluble unit dose article dissolves - film residue Test Method: This test method describes a water-soluble unit dose article dissolution test that evaluates the amount of undissolved water-soluble film residue. More specifically, this method is designed to evaluate the relevant dissolution characteristics of a water-soluble unit dose article for washing under stressed washing machine conditions. For this method, an Electrolux programmable washing machine model W565H (manufactured by Calderon Textiles, LLC, 6131 W 80th Street Indianapolis, IN 46278) was used that contained a ballast load fabric with a mixture of cotton and polycotton pieces. The ballast load fabric consisted of a two-ply swatch of cotton and polycotton knit with a size of approximately 50 x 50 cm.

[0148] Orange Pouch: New cotton white ballast load fabric from Calderon 50x50cm was divided into portions of up to 3.0 kg (approximately 25 items of ballast cotton) and prepared to be dyed orange by the machine dyeing process using a commercial dye solution. Any standard domestic washing machine using a standard cotton cycle at 40°C can be used to dye the load fabric. 350g of Dylon Fresh Orange Machine Dye All-in-One is added to the washing machine drum. Salt may be added according to the dye package instructions.

[0149] As a result, the drum was manually moved back and forth until no more dye was visible. As a result, the cotton ballast (50 cm x 50 cm in size) of 25 items was evenly distributed on the drum without folding the items. A standard cotton cycle was run at 40°C with 15 gpg water hardness. After the cycle was completed, 75 g of Ariel Professional powder was added to the dispenser and a standard cotton cycle was run at 40°C with 15 gpg water hardness. After the completion of this cycle 2, an additional standard cotton cycle was run at 40°C with 15 gpg water hardness without detergent, followed by line drying of the items.

[0150] NOTE: New Calderon loads should be desized before they are colored by adding 25 items to a front-loading Miele washing machine and running two short cotton cycles at 60°C (approximately 1 hour 30 minutes duration) with 50g of Ariel Sensitive powder at 15 gpg water hardness, followed by two more short cotton cycles at 60°C (approximately 1 hour 30 minutes duration) at 15 gpg water hardness without detergent, followed by tumble drying.

[0151] The orange fabric is then cut into a 48 x 48 cm piece, folded in half, cut in half and sewn at the sides to form four equal 22 x 22 cm pouches open at the top. One test product of the preconditioned water soluble unit dose article is placed in the lower right corner of the orange pouch and the pouch is sewn closed. The water soluble unit dose article must be preconditioned at 23°C and 50% rH for a minimum of two weeks prior to testing.

[0152] Loads: Four loads of 3 kg mixed cotton (13 pieces) and polycotton (10 pieces) were desized prior to use by washing on a short cotton cycle at 60° C. with 79 g Ariel Professional detergent at 15 gpg water hardness, followed by another short cotton cycle at 60° C. without detergent at 15 gpg water hardness, and finally tumble drying. Each load of 3.0 kg was pretreated twice by washing with four Ariel pods on a "pre-wet" cycle, followed by washing without detergent in the "dissolution program" described below, and finally tumble drying.

[0153] An Electrolux W565 programmable washing machine was programmed with two programs. The first program was designed to evenly wet the load of fabrics (the Pre-Wet Program). The second program (the Dissolve Program) was utilized to simulate a 15 minute Western stress cycle setting, followed by a drain and start of a 3 minute spin at 1100 rpm.

[0154] [Table 4]

[0155] A load of 13 pieces of 50x50cm cotton and 10 pieces of 27x27cm polycotton (weight 3.0+ / -0.15kg) was uniformly placed in an Electrolux W565 washing machine and the pre-wet program was run twice.

[0156] After the pre-wet program, the wet ballast is removed from the drum, and four orange pouches, each containing a different test group water-soluble unit dose article, are lined up at the bottom of the drum, so that four different test products are tested at once in the same washing machine, making the test environment as reproducible as possible across test groups. 10g of suds suppressor (Dowsil GP-4314 silicone suds suppressor available from Dow Corning) is added to the dispenser, and the wet load cloth is placed on the orange pouch without moving the drum. The dissolving program is started. At the end of the entire program, the orange pouch is transferred to a scoring room (with D65 lighting conditions) and evaluated for residue by a professional scorer.

[0157] The orange pouches are cut and visually scored according to a 0-7 scale (0 = no film residue, 7 = complete pouch residue) within 30 min after the end of each experiment. The final score is calculated as the average of the four external replicates, i.e., four different washer experiments, repeated twice (average of 8 scores).

[0158] Test results: The results summarized in Table 4 clearly show that the water-soluble unit dose article (Invention Example 1) comprising a water-soluble test film comprising a polyvinyl alcohol-based polymer resin comprised of a homopolymer blend having an average viscosity profile according to the present invention, despite having superior pouch strength, does not exhibit reduced dissolution compared to the tested water-soluble unit dose articles (Comparative Examples 5-6) comprising a water-soluble test film comprising a polyvinyl alcohol-based polymer resin comprised of a polyvinyl alcohol homopolymer blend having an average viscosity profile outside the range of the present invention, as well as compared to the tested water-soluble unit dose articles (Comparative Examples 2-3) comprising a water-soluble test film comprising a polyvinyl alcohol-based polymer resin comprising 15% anionic polyvinyl alcohol copolymer.

[0159] [Table 5] * Lower is better

[0160] Overall conclusion: From the data summarized across the different examples, it is clear that water-soluble films comprising polyvinyl alcohol based resins consisting of polyvinyl alcohol homopolymer blends containing a viscosity profile according to the present invention do not form a foam layer upon sealing solvent application and provide superior sealing and pouch strength profiles while not resulting in reduced dissolution compared to comparative water-soluble film compositions outside the scope of the present invention.

Claims

1. 1. A water-soluble unit dose article comprising at least a first compartment and a laundry detergent composition, said laundry detergent composition being contained within said at least a first compartment, said unit dose article comprising: a. a first water-soluble film, the first water-soluble film having a first surface and a second surface, the first water-soluble film comprising a first polyvinyl alcohol resin, the first polyvinyl alcohol resin comprising: i. 10% to 65% by weight of the first polyvinyl alcohol resin of a first polyvinyl alcohol polymer, the first polyvinyl alcohol polymer comprising carboxylated anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units, the carboxylated anionic monomer units being derived from a member selected from the group consisting of maleic acid, monoalkyl maleates, dialkyl maleates, maleic anhydride, and combinations thereof; and ii. a first water-soluble film comprising 35% to 90% by weight of the first polyvinyl alcohol resin of a second polyvinyl alcohol polymer, the second polyvinyl alcohol polymer being a homopolymer, the homopolymer consisting of vinyl alcohol monomer units and, optionally, vinyl acetate monomer units; b. a second water-soluble film, the second water-soluble film having a first surface and a second surface, the second water-soluble film comprising a second polyvinyl alcohol resin, the second polyvinyl alcohol resin comprising: ii. a second water-soluble film comprising a 100% by weight polyvinyl alcohol homopolymer blend of said second polyvinyl alcohol resin, said homopolymer consisting of vinyl alcohol monomer units and optionally vinyl acetate monomer units; the second polyvinyl alcohol resin comprises a blend of a first polyvinyl alcohol homopolymer and a second polyvinyl alcohol homopolymer; the first polyvinyl alcohol homopolymer and the second polyvinyl alcohol homopolymer are present in a relative weight ratio of from 70 / 30 to 50 / 50; a. the first polyvinyl alcohol homopolymer has an average viscosity in the range of 11 mPa.s to 20 mPa.s, measured as a 4% polyvinyl alcohol polymer solution in deionized water at 20° C.; b. the second polyvinyl alcohol homopolymer has an average viscosity in the range of 1 mPa.s to 10 mPa.s, measured as a 4% polyvinyl alcohol polymer solution in deionized water at 20°C; the second polyvinyl alcohol resin has an average 4% solution viscosity in deionized water at 20° C. ranging from 8 mPa.s to less than 12 mPa.s; a first side of said first water-soluble film sealed to a second side of said second water-soluble film to create said at least a first compartment between said first water-soluble film and said second water-soluble film.

2. 2. The water soluble unit dose article of claim 1, wherein the first polyvinyl alcohol resin comprises 30% to 50% of a first polyvinyl alcohol polymer by weight of the first polyvinyl alcohol resin and 50% to 70% of a second polyvinyl alcohol polymer by weight of the first polyvinyl alcohol resin.

3. a. the first polyvinyl alcohol homopolymer has an average viscosity in the range of 11 mPa.s to 15 mPa.s, measured as a 4% polyvinyl alcohol polymer solution in deionized water at 20° C.; The water soluble unit dose article of claim 1, wherein the second polyvinyl alcohol homopolymer has an average viscosity in the range of 5 mPa.s to 10 mPa.s, measured as a 4% polyvinyl alcohol polymer solution in deionized water at 20° C.

4. The water soluble unit dose article of any one of claims 1 to 3, wherein each said polyvinyl alcohol homopolymer independently has an average degree of hydrolysis ranging from 75% to 99%.

5. a. the first polyvinyl alcohol resin is present in the range of 50% to 95% by weight of the first water-soluble film; or b. the second polyvinyl alcohol resin is present in the range of 50% to 95% by weight of the second water-soluble film; or c. The water soluble unit dose article of any one of claims 1 to 4, which is a combination thereof.

6. The water-soluble unit dose article of any one of claims 1 to 5, wherein the carboxylated anionic monomer units in the first water-soluble film are derived from monoalkyl maleate units.

7. The first polyvinyl alcohol polymer in the first water-soluble film is a. an average 4% solution viscosity at 20°C, measured as a 4% solution of the polyvinyl alcohol polymer in deionized water at 20°C, of ​​between 10 mPa.s and 40 mPa.s; or b. An average degree of hydrolysis between 60% and 99%, or c) A water-soluble unit dose article according to any one of claims 1 to 6, characterized by a combination thereof.

8. the second polyvinyl alcohol polymer in the first water-soluble film is d. an average 4% solution viscosity at 20° C., measured as a 4% solution of the polyvinyl alcohol polymer in deionized water at 20° C., of 3 mPa.s to 30 mPa.s; or e. an average degree of hydrolysis of 60% to 99%, or f. The water-soluble unit dose article according to any one of claims 1 to 7, characterized by a combination thereof.

9. 9. The water soluble unit dose article of any one of claims 1 to 8, wherein the relative weight ratio of the first polyvinyl alcohol polymer and the second polyvinyl alcohol polymer in the first water soluble film is from 70 / 30 to 50 / 50.

10. 10. The water-soluble unit dose article of any one of claims 1 to 9, wherein the first water-soluble film and the second water-soluble film each independently comprise from 0.1% to 2.5% by weight of the water-soluble film of a surfactant.

11. 11. The water-soluble unit dose article of claim 1, wherein the first water-soluble film and the second water-soluble film each individually have a residual moisture content of at least 4% by weight of the water-soluble film as measured by Karl Fischer titration.

12. 12. The water soluble unit dose article of any one of claims 1-11, wherein each film independently comprises one or more ingredients selected from the group consisting of plasticizers, plasticizer compatibilizers, lubricants, release agents, fillers, extenders, crosslinkers, antiblocking agents, antioxidants, detackifying agents, antifoaming agents, nanoparticles, bleaching agents, aversive agents, surfactants, and combinations thereof.

13. 13. The water soluble unit dose article of claim 12, wherein each film independently comprises one or more plasticizers in an amount ranging from 5% to 50% by weight of the individual film.

14. 14. The water soluble unit dose article of claim 13, wherein the plasticizer is selected from the group consisting of sorbitol, glycerol, dipropylene glycol, polyethylene glycol, trimethylolpropane, and mixtures thereof.

15. The water-soluble unit dose article of any one of claims 1 to 14, wherein the first water-soluble film and the second water-soluble film are sealed via solvent sealing, heat sealing, or a combination thereof.

16. The water-soluble unit dose article of any one of claims 1 to 15, wherein the unit dose article comprises at least a second compartment between the first water-soluble film and the second water-soluble film.

17. The water soluble unit dose article of any one of claims 1 to 16, wherein the laundry detergent composition is a liquid laundry detergent composition.

18. A process for producing a water-soluble unit dose article according to any one of claims 1 to 17, comprising the steps of: a. deforming the first water-soluble film in a mold via thermoforming, vacuum forming, or a combination thereof to create an open cavity; b. filling at least one of said open cavities with said laundry detergent composition; c. closing the filled open cavity with the second water-soluble film; and d. sealing said first water-soluble film and said second water-soluble film to create said water-soluble unit dose article.

Citation Information

Patent Citations

  • Aqueous delayed release capsules, related methods and related articles

    JP2016540836A

  • Aqueous delayed release capsules, related methods and related articles

    JP2017500376A

  • Water-soluble unit dose article made from a combination of different films and containing a household care composition

    JP2019519440A

  • Water-soluble unit dose article made from a combination of different films and containing a household care composition

    JP2019520273A

  • Pouches having water-soluble films made from polyvinyl alcohol polymer blends, and related methods

    US10619042B2